Roller hearth kiln

The method of producing positive electrode active materials for lithium-ion batteries by incorporating lithium, a transition metal, oxygen, and fluorine, with a fixation suppression step during heating, addresses the challenges of high costs, low productivity, and crystal structure stability, resulting in improved battery performance and safety.

JP2025071140APending Publication Date: 2025-05-02SEMICON ENERGY LAB CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2025023572
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-12-10
Filing Date
2025-02-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The production of positive electrode active materials for lithium-ion batteries is hindered by high costs, low productivity, and the challenge of maintaining crystal structure stability during repeated charge and discharge cycles.

Method used

A method for producing a positive electrode active material involving the use of lithium, a transition metal, oxygen, and fluorine, with a fixation suppression step during heating to prevent adhesion, such as agitation in a rotary furnace or vibration of the container, and multiple heating steps with intermediate disintegration.

Benefits of technology

This method enhances productivity, maintains crystal structure integrity, and improves cycle characteristics and charge/discharge capacity of the positive electrode active material, leading to more reliable and safe secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071140000001_ABST
    Figure 2025071140000001_ABST
Patent Text Reader

Abstract

To provide a production method for a cathode active material with good productivity, or a production device capable of producing a cathode active material with good productivity.SOLUTION: A production method for a cathode active material containing lithium, a transition metal, oxygen, and fluorine comprises a fixation inhibition step during heating of a material to be processed. Examples of the fixation inhibition step include stirring by rotating a furnace during heating, stirring by vibrating a container containing the material to be processed during heating, and grinding performed between a plurality of heating steps. Using these production methods allows a cathode active material having a good distribution of an additive on a surface layer to be produced.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One embodiment of the present invention relates to an object, a method, or a manufacturing method. Alternatively, the present invention relates to a process, a machine, a manufacture, or a composition of matter. One embodiment of the present invention relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, an electronic device, or a manufacturing method thereof.

[0002] In this specification, the term "electronic device" refers to any device having a power storage device, and an electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all classified as electronic devices. [Background technology]

[0003] In recent years, various types of power storage devices have been actively developed, such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries, all-solid-state batteries, etc. In particular, the demand for high-output, high-capacity lithium-ion secondary batteries has rapidly expanded in line with the development of the semiconductor industry, and they have become indispensable in the modern information society as a rechargeable energy source.

[0004] With the increase in demand, there is a demand for improving the productivity of lithium-ion batteries and their materials. As part of this, development of an efficient method for producing a positive electrode active material, which is one of the materials for lithium-ion batteries, is underway. For example, Patent Document 1 discloses a method for producing a positive electrode active material using a rotary kiln capable of continuous processing.

[0005] Furthermore, research into the crystal structure of positive electrode active materials has also been conducted (Non-Patent Documents 1 to 3).

[0006] X-ray diffraction (XRD) is one of the techniques used to analyze the crystal structure of positive electrode active materials. XRD data can be analyzed by using the Inorganic Crystal Structure Database (ICSD) introduced in Non-Patent Document 4. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. WO2012 / 098724 Brochure [Non-patent literature]

[0008] [Non-Patent Document 1] Toyoki Okumura et al, “Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation”, Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-Patent Document 2] Motohashi, T. et al, “Electronic phase diagram of the layered cobalt oxide system LixCoO2(0.0≦x≦1.0)”, Physical Review B, 80(16) ,2009, 165114 [Non-Patent Document 3] Zhaohui Chen et al, “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society, 2002, 149(12) A1604-A1609 [Non-Patent Document 4] Belsky, A. et al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., 2002, B58 364-369. Summary of the Invention [Problem to be solved by the invention]

[0009] Positive electrode active materials are expensive materials in lithium-ion secondary batteries, and the effect of improving productivity is high. At the same time, there is a strong demand for high performance (for example, high capacity, improved cycle characteristics, improved reliability or safety).

[0010] In view of the above, an object of one embodiment of the present invention is to provide a method for manufacturing a positive electrode active material with high productivity. Another object is to provide a manufacturing apparatus capable of manufacturing a positive electrode active material with high productivity. Another object is to provide a method for manufacturing a positive electrode active material whose crystal structure is not easily destroyed even after repeated charging and discharging. Another object is to provide a method for manufacturing a positive electrode active material with excellent charge and discharge cycle characteristics. Another object is to provide a method for manufacturing a positive electrode active material with large charge and discharge capacity. Another object is to provide a secondary battery with high reliability or safety.

[0011] Another object of one embodiment of the present invention is to provide a positive electrode active material, a power storage device, or a manufacturing method thereof.

[0012] Note that the description of these problems does not preclude the existence of other problems. Note that one embodiment of the present invention does not necessarily solve all of these problems. Note that it is possible to extract problems other than these from the description of the specification, drawings, and claims. [Means for solving the problem]

[0013] One embodiment of the present invention is a method for producing a positive electrode active material containing lithium, a transition metal, oxygen, and fluorine, the method including a step of preventing adhesion during heating of a workpiece.

[0014] In the above, the adhesion suppression step is preferably performed by stirring the material by rotating the furnace during heating, or by vibrating a container containing the material during heating.

[0015] Another embodiment of the present invention is a method for producing a positive electrode active material containing lithium, a transition metal, oxygen, and fluorine, the method including a sticking suppression step between multiple heating steps.

[0016] In the above, the adhesion suppression step is preferably at least one of stirring by vibrating a container containing the object to be treated during heating, and crushing carried out between a plurality of heating steps.

[0017] In the above, it is preferable to put ceramic balls into the furnace together with the object to be treated.

[0018] Another embodiment of the present invention is a rotary kiln that continuously processes materials fed into the kiln, the kiln having a kiln body, a mill, a first heating means, a second heating means, a first raw material supplying means, a second raw material supplying means, and an atmosphere control means, the kiln body being substantially cylindrical and having a function of stirring the materials to be treated by rotating, the kiln body having an upstream portion and a downstream portion, the kiln body having a function of retaining the materials to be treated in the upstream portion for 1 hour or more and 100 hours or less, and the kiln body having a function of retaining the materials to be treated in the downstream portion for 1 hour or more and 100 hours or less. the mill has a function of suppressing adhesion of the workpiece, the first heating means has a function of heating the upstream portion of the kiln body to between 800°C and 1100°C, the second heating means has a function of heating the downstream portion of the kiln body to between 500°C and 1130°C, the first raw material supply means has a function of supplying the workpiece to the upstream portion of the kiln body, the second raw material supply means has a function of supplying additional raw material to the downstream portion of the kiln body, and the atmosphere control means is an oxygen-containing gas introduction line that introduces an oxygen-containing gas into the interior of the kiln body.

[0019] Another embodiment of the present invention is a kiln that continuously processes materials fed into it, the kiln having a kiln body, a first mill, a second mill, a first heating means, a second heating means, and a raw material supplying means, the kiln body is approximately cylindrical and has a scraper blade inside, the scraper blade having a function of stirring the materials to be treated, the kiln body has an upstream portion and a downstream portion, and has a function of retaining the materials to be treated in the upstream portion for 1 hour or more and 100 hours or less, and a function of retaining the materials to be treated in the downstream portion for 1 hour or more and 100 hours or less, the first mill and the second mill are provided between the upstream portion and the downstream portion, and have a function of suppressing adhesion of the materials to be treated, the first heating means has a function of heating the upstream portion of the kiln body to 800°C or more and 1100°C or less, the second heating means has a function of heating the downstream portion of the kiln body to 500°C or more and 1130°C or less, and the raw material supplying means has a function of supplying the materials to be treated to the upstream portion of the kiln body.

[0020] Another aspect of the present invention is a roller hearth kiln that continuously treats materials contained in containers, the roller hearth kiln having a tunnel-shaped kiln body, multiple rollers, first heating means, second heating means, atmosphere control means, and sticking prevention means, the multiple rollers have a function of transporting the containers, the kiln body has an upstream portion and a downstream portion along the transport direction of the multiple rollers, the first heating means has a function of heating the upstream portion to a temperature of 800°C or higher and 1100°C or lower, the second heating means has a function of heating the downstream portion to a temperature of 500°C or higher and 1130°C or lower, the atmosphere control means is an oxygen-containing gas inlet line that introduces an oxygen-containing gas into the kiln body, and the sticking prevention means has a function of vibrating the container.

[0021] Another embodiment of the present invention is a heating furnace for batch processing of workpieces contained in a container, the heating furnace having a heating means, a space within the heating furnace, an atmosphere control means, and an adhesion suppression means, the heating means having a function of heating the space within the heating furnace to 800°C or higher and 1100°C or lower, the atmosphere control means being an oxygen-containing gas inlet line for introducing an oxygen-containing gas into the space within the heating furnace, and the adhesion suppression means having a function of vibrating the container. Effect of the Invention

[0022] According to one embodiment of the present invention, a method for manufacturing a positive electrode active material with high productivity can be provided. Alternatively, a manufacturing apparatus capable of manufacturing a positive electrode active material with high productivity can be provided. Alternatively, a method for manufacturing a positive electrode active material whose crystal structure is not easily destroyed even after repeated charging and discharging can be provided. Alternatively, a method for manufacturing a positive electrode active material having excellent charge and discharge cycle characteristics can be provided. Alternatively, a method for manufacturing a positive electrode active material having a large charge and discharge capacity can be provided. Alternatively, a secondary battery with high reliability or safety can be provided.

[0023] According to one embodiment of the present invention, a positive electrode active material, a power storage device, or a manufacturing method thereof can be provided.

[0024] Note that the description of these effects does not preclude the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of these effects. Note that effects other than these will become apparent from the description in the specification, drawings, claims, etc., and it is possible to extract effects other than these from the description in the specification, drawings, claims, etc. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a diagram illustrating an example of a method for producing a positive electrode active material. [Diagram 2] FIG. 2 is a diagram illustrating an example of a method for producing a positive electrode active material. [Diagram 3] FIG. 3 is a diagram illustrating an example of a method for producing a positive electrode active material. [Figure 4] FIG. 4 is a diagram illustrating an example of a method for producing a positive electrode active material. [Diagram 5] FIG. 5A is a top view of the positive electrode active material, and FIG. 5B is a cross-sectional view of the positive electrode active material. [Figure 6] FIG. 6 is a diagram illustrating the charge depth and the crystal structure of the positive electrode active material. [Figure 7] FIG. 7 is a diagram illustrating the charge depth and the crystal structure of the positive electrode active material of the comparative example. [Figure 8] FIG. 8 shows an XRD pattern calculated from the crystal structure. [Figure 9] 9A to 9C show the lattice constants calculated from XRD. [Figure 10] 10A to 10C show the lattice constants calculated from XRD. [Figure 11] 11A and 11B are views for explaining an example of a manufacturing apparatus, and Fig. 11C is a view for explaining a cross section of the manufacturing apparatus. [Figure 12] 12A and 12B are diagrams illustrating an example of a manufacturing apparatus. [Figure 13] Fig. 13A is a diagram for explaining an example of a manufacturing apparatus, Fig. 13B is a diagram for explaining the arrangement of rollers, and Fig. 13C is a diagram for explaining an example of a manufacturing apparatus. [Figure 14] 14A and 14B are diagrams illustrating an example of a manufacturing apparatus. [Figure 15] 15A and 15B are cross-sectional views of an active material layer in which a graphene compound is used as the conductive material. [Figure 16] 16A and 16B are diagrams illustrating an example of a secondary battery. [Figure 17] 17A to 17C are diagrams illustrating an example of a secondary battery. [Figure 18] 18A and 18B are diagrams illustrating an example of a secondary battery. [Figure 19] 19A to 19C are diagrams illustrating a coin-type secondary battery. [Figure 20] 20A to 20D are diagrams illustrating a cylindrical secondary battery. [Figure 21] 21A and 21B are diagrams illustrating an example of a secondary battery. [Figure 22] 22A to 22D are diagrams illustrating an example of a secondary battery. [Figure 23] 23A and 23B are diagrams illustrating an example of a secondary battery. [Figure 24] FIG. 24 is a diagram illustrating an example of a secondary battery. [Diagram 25] 25A to 25C are diagrams illustrating a laminated type secondary battery. [Figure 26] 26A and 26B are diagrams illustrating a laminated type secondary battery. [Figure 27] FIG. 27 is a diagram showing the appearance of a secondary battery. [Figure 28] FIG. 28 is a diagram showing the appearance of a secondary battery. [Figure 29] 29A to 29C are diagrams illustrating a method for manufacturing a secondary battery. [Diagram 30] 30A to 30H are diagrams illustrating an example of an electronic device. [Diagram 31] 31A to 31C are diagrams illustrating an example of an electronic device. [Diagram 32]FIG. 32 is a diagram illustrating an example of an electronic device. [Diagram 33] 33A to 33C are diagrams illustrating an example of an electronic device. [Diagram 34] 34A to 34C are diagrams showing an example of an electronic device. [Diagram 35] 35A to 35C are diagrams illustrating an example of a vehicle. [Diagram 36] 36A to 36C are SEM images of the positive electrode active material produced in Example 1. [Figure 37] 37A and 37B are graphs showing the cycle characteristics of the positive electrode active material prepared in Example 1. [Figure 38] 38A and 38B are graphs showing the cycle characteristics of the positive electrode active material prepared in Example 1. [Figure 39] 39A and 39B are graphs showing the cycle characteristics of the positive electrode active material prepared in Example 1. [Diagram 40] 40A and 40B are graphs showing the cycle characteristics of the positive electrode active material prepared in Example 1. [Diagram 41] 41A and 41B are graphs showing the cycle characteristics of the positive electrode active material prepared in Example 1. [Diagram 42] 42A and 42B are graphs showing the cycle characteristics of the positive electrode active material prepared in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following description, and it will be easily understood by those skilled in the art that the form and details of the present invention can be modified in various ways. Furthermore, the present invention is not to be interpreted as being limited to the description of the embodiments shown below.

[0027] In addition, in this specification and the like, Miller indices are used to represent crystal planes and directions. Individual planes indicating crystal planes are represented in ( ). In crystallography, crystal planes, directions, and space groups are represented by adding a superscript bar to the numbers, but in this specification and the like, due to restrictions on notation in the application, the numbers may be represented by adding a - (minus sign) before them instead of adding a bar above them.

[0028] In this specification, the layered rock-salt type crystal structure of a composite oxide containing lithium and a transition metal refers to a crystal structure having a rock-salt type ion arrangement in which cations and anions are alternately arranged, and in which the transition metal and lithium are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. Defects such as deficiencies of cations or anions may be present. Strictly speaking, the layered rock-salt type crystal structure may have a structure in which the lattice of the rock-salt type crystal is distorted.

[0029] In this specification and the like, the rock salt type crystal structure refers to a structure in which cations and anions are arranged alternately, and it is acceptable for there to be a deficiency of cations or anions.

[0030] In this specification, the theoretical capacity of a positive electrode active material refers to the amount of electricity when all of the lithium that can be inserted and removed from the positive electrode active material is removed. For example, the theoretical capacity of LiCoO2 is 274 mAh / g, the theoretical capacity of LiNiO2 is 274 mAh / g, and the theoretical capacity of LiMn2O4 is 148 mAh / g.

[0031] In this specification and the like, the depth of charge when all intercalable and deintercalable lithium is intercalated is defined as 0, and the depth of charge when all intercalable and deintercalable lithium contained in the positive electrode active material is deintercalated is defined as 1.

[0032] In addition, in the present specification and the like, as a secondary battery using the positive electrode and the positive electrode active material of one embodiment of the present invention, an example in which lithium metal is used as a counter electrode is sometimes shown, but the secondary battery of one embodiment of the present invention is not limited thereto. Other materials, for example, graphite, lithium titanate, and the like may be used as a negative electrode. The properties of the positive electrode and the positive electrode active material of one embodiment of the present invention, such as the crystal structure being unlikely to be broken even when repeatedly charged and discharged, and good cycle characteristics being obtained, are not affected by the material of the negative electrode. In addition, although an example in which the secondary battery of one embodiment of the present invention is charged and discharged at a relatively high voltage, such as a charging voltage of 4.6 V, with a lithium counter electrode is sometimes shown, charging and discharging at a lower voltage may be performed. When charging and discharging at a lower voltage, it is expected that the cycle characteristics will be further improved than those shown in the present specification and the like.

[0033] In this specification, the term "adhesion" refers to particles gathering together and solidifying through heating. This bonding between particles is presumed to be due to ionic bonds or van der Waals forces, but regardless of the heating temperature, crystal state, element distribution state, etc., the term "adhesion" refers to particles simply gathering together and solidifying.

[0034] In this specification, the term "kiln" refers to a device for heating an object to be treated. For example, a furnace, a kiln, a heating device, etc. may be used instead of a kiln.

[0035] (Embodiment 1) In this embodiment, an example of a manufacturing method of a positive electrode active material of one embodiment of the present invention will be described with reference to Fig. 1 to Fig. 4. The manufacturing method described in this embodiment is particularly effective when the amount of the positive electrode active material to be manufactured is large, for example, 10 g or more.

[0036] <Step S11> In step S11 of FIG. 1, first, a lithium source and a transition metal M source are prepared as materials for a composite oxide (LiMO2) having lithium, a transition metal M, and oxygen.

[0037] As the lithium source, for example, lithium carbonate, lithium fluoride, lithium hydroxide, etc. can be used.

[0038] As the transition metal M, it is preferable to use a metal that can form a layered rock-salt type composite oxide belonging to the space group R-3m together with lithium. For example, at least one of manganese, cobalt, and nickel can be used. In other words, as the source of the transition metal M, only cobalt may be used, only nickel may be used, two types of cobalt and manganese, two types of cobalt and nickel may be used, or three types of cobalt, manganese, and nickel may be used.

[0039] When using metals capable of forming a layered rock-salt type composite oxide, it is preferable to mix cobalt, manganese, and nickel in a ratio that allows a layered rock-salt type crystal structure to be formed. Aluminum may also be added to these transition metals in a ratio that allows a layered rock-salt type crystal structure to be formed.

[0040] As the transition metal M source, oxides, hydroxides, etc. of the above-mentioned metals exemplified as the transition metal M can be used. As the cobalt source, for example, cobalt oxide, cobalt hydroxide, etc. can be used. As the manganese source, manganese oxide, manganese hydroxide, etc. can be used. As the nickel source, nickel oxide, nickel hydroxide, etc. can be used. As the aluminum source, aluminum oxide, aluminum hydroxide, etc. can be used.

[0041] <Step S12> Next, in step S12, the lithium source and the transition metal M source are crushed and mixed. Mixing can be performed in a dry or wet manner. For example, a ball mill, a bead mill, or the like can be used for mixing. When using a ball mill, it is preferable to use zirconia balls as the media.

[0042] <Step S13> Next, in step S13, the mixed material is heated. This step is sometimes called sintering or first heating to distinguish it from the subsequent heating step. Heating is preferably performed at 800°C or higher and lower than 1100°C, more preferably at 900°C or higher and 1000°C or lower, and even more preferably at about 950°C. If the temperature is too low, the decomposition and melting of the lithium source and the transition metal M source may be insufficient. On the other hand, if the temperature is too high, defects may occur due to excessive reduction of the transition metal M responsible for the redox reaction, or lithium evaporating. For example, when cobalt is used as the transition metal M, defects may occur in which cobalt becomes divalent.

[0043] The heating time can be, for example, 1 hour or more and 100 hours or less, and preferably 2 hours or more and 20 hours or less. The shorter the heating time, the better the productivity. However, if the heating time is too long, the decomposition and melting of the lithium source and the transition metal M source may be insufficient. The firing is preferably carried out in an atmosphere with little water, such as dry air (for example, a dew point of -50°C or less, more preferably -100°C or less). For example, it is preferable to heat at 1000°C for 10 hours, with a temperature rise of 200°C / h and a flow rate of the dry atmosphere of 10L / min. The heated material can then be cooled to room temperature. For example, it is preferable to set the temperature drop time from a specified temperature to room temperature to 10 hours or more and 50 hours or less.

[0044] However, cooling to room temperature in step S13 is not essential, and cooling may be performed to a temperature higher than room temperature if there is no problem in performing the subsequent steps S41 to S44.

[0045] <Step S14> Next, in step S14, the sintered material is recovered to obtain a composite oxide (LiMO2) containing lithium, a transition metal M, and oxygen. Specifically, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium cobalt oxide in which part of the cobalt is replaced with manganese, lithium cobalt oxide in which part of the cobalt is replaced with nickel, or lithium nickel-manganese-cobalt oxide is obtained.

[0046] Alternatively, a composite oxide containing lithium, a transition metal M, and oxygen that has been synthesized in advance may be used in step S14. In this case, steps S11 to S13 may be omitted.

[0047] For example, lithium cobalt oxide (product name: Cellseed C-10N) manufactured by Nippon Chemical Industry Co., Ltd. can be used as a pre-synthesized composite oxide. This is lithium cobalt oxide with a median diameter (D50) of about 12 μm, and in impurity analysis by glow discharge mass spectrometry (GD-MS), the magnesium concentration and fluorine concentration are 50 ppm wt or less, the calcium concentration, aluminum concentration and silicon concentration are 100 ppm wt or less, the nickel concentration is 150 ppm wt or less, the sulfur concentration is 500 ppm wt or less, the arsenic concentration is 1100 ppm wt or less, and the concentrations of other elements other than lithium, cobalt and oxygen are 150 ppm wt or less.

[0048] Alternatively, lithium cobalt oxide (product name: Cellseed C-5H) manufactured by Nippon Chemical Industry Co., Ltd. can be used. This is a lithium cobalt oxide with a median diameter (D50) of approximately 6.5 μm, and in impurity analysis by GD-MS, the concentration of elements other than lithium, cobalt, and oxygen is approximately the same as or lower than that of C-10N.

[0049] In this embodiment, cobalt is used as the metal M, and pre-synthesized lithium cobalt oxide (Cellseed C-10N manufactured by Nippon Chemical Industry Co., Ltd.) is used.

[0050] <Step S21> Next, in step S21, a fluorine source and a magnesium source are prepared as materials for the mixture 902. It is also preferable to prepare a lithium source.

[0051] Examples of fluorine sources that can be used include lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF2), lanthanum fluoride (LaF3), and sodium aluminum hexafluoride (Na3AlF6). The fluorine source is not limited to a solid, and may be, for example, fluorine (F2), carbon fluoride, sulfur fluoride, oxygen fluoride (OF2, O2F2, O3F2, O4F2, O2F), etc., which may be mixed into the atmosphere in the heating step described below. A mixture of multiple fluorine sources may also be used. Among them, lithium fluoride is preferable because it has a relatively low melting point of 848°C and is easily melted in the annealing step described below.

[0052] As the chlorine source, for example, lithium chloride, magnesium chloride, etc. can be used.

[0053] As the magnesium source, for example, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. can be used.

[0054] Examples of the lithium source that can be used include lithium fluoride, lithium carbonate, and lithium hydroxide. That is, lithium fluoride can be used as both a lithium source and a fluorine source. Magnesium fluoride can be used as both a fluorine source and a magnesium source.

[0055] In this embodiment, lithium fluoride LiF is prepared as the fluorine source, and magnesium fluoride MgF2 is prepared as the fluorine source and magnesium source. When lithium fluoride LiF and magnesium fluoride MgF2 are mixed at a molar ratio of about LiF:MgF2=65:35, the effect of lowering the melting point is maximized. On the other hand, if the amount of lithium fluoride is large, there is a concern that the lithium becomes excessive and the cycle characteristics deteriorate. Therefore, the molar ratio of lithium fluoride LiF and magnesium fluoride MgF2 is preferably LiF:MgF2=x:1 (0≦x≦1.9), more preferably LiF:MgF2=x:1 (0.1≦x≦0.5), and even more preferably LiF:MgF2=x:1 (near x=0.33). In this specification, etc., "near" refers to a value that is greater than 0.9 times and less than 1.1 times the value.

[0056] In addition, when the next mixing and grinding process is performed in a wet manner, a solvent is prepared. As the solvent, a ketone such as acetone, an alcohol such as ethanol or isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent that is less likely to react with lithium. In this embodiment, acetone is used.

[0057] <Step S22> Next, in step S22, the materials of the mixture 902 are mixed and pulverized. Mixing can be performed in a dry or wet manner, but the wet method is preferred because it allows for finer pulverization. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconia balls as the media. It is preferable to thoroughly perform this mixing and pulverization process to finely pulverize the mixture 902.

[0058] <Step S23> Next, in step S23, the mixed and crushed materials are collected to obtain a mixture 902.

[0059] The mixture 902 preferably has a D50 (median diameter) of, for example, 600 nm to 20 μm, more preferably 1 μm to 10 μm. If the mixture 902 is finely pulverized in this manner, when it is mixed with a composite oxide having lithium, transition metal M, and oxygen in a later step, the mixture 902 can be easily attached uniformly to the surface of the composite oxide. If the mixture 902 is attached uniformly to the surface of the composite oxide, it is preferable because fluorine and magnesium can be easily distributed thoroughly near the surface of the composite oxide after heating. If there is a region near the surface that does not contain fluorine and magnesium, it may be difficult to obtain an O3' type crystal structure in a charged state, which will be described later.

[0060] <Step S41> Next, in step S41, LiMO2 obtained in step S14 is mixed with mixture 902. The ratio of the number of transition metal atoms M in composite oxide LiMO2 containing lithium, transition metal, and oxygen to the number of magnesium atoms Mg in mixture 902 is preferably M:Mg=100:y (0.1≦y≦6), and more preferably M:Mg=100:y (0.3≦y≦3).

[0061] The mixing in step S41 is preferably performed under milder conditions than the mixing in step S12 in order not to destroy the particles of the composite oxide LiMO2. For example, the mixing is preferably performed under conditions of a lower rotation speed or shorter time than in step S12. Also, it can be said that the dry method generally has milder conditions than the wet method. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconia balls as the media, for example.

[0062] <Step S42> Next, in step S42, the mixed materials are collected to obtain a mixture 903.

[0063] In this embodiment, a method of adding a mixture of lithium fluoride and magnesium fluoride to lithium cobalt oxide with few impurities is described, but one embodiment of the present invention is not limited to this. Instead of the mixture 903 in step S42, a starting material of lithium cobalt oxide to which a magnesium source, a fluorine source, and the like are added and baked may be used. In this case, there is no need to separate the steps S11 to S14 from the steps S21 to S23, and therefore the process is simple and has high productivity.

[0064] Alternatively, lithium cobalt oxide to which magnesium and fluorine have been added in advance may be used. If lithium cobalt oxide to which magnesium and fluorine have been added is used, the steps S11 to S14 can be omitted, which is more convenient.

[0065] Furthermore, a magnesium source and a fluorine source may be further added to lithium cobalt oxide to which magnesium and fluorine have already been added.

[0066] <Step S43> Next, in step S43, the mixture 903 is heated in an atmosphere containing oxygen. The heating is preferably performed in a manner that has an anti-adhesion effect so that the particles of the mixture 903 do not adhere to each other. This step may be called annealing, anti-adhesion annealing, or second heating to distinguish it from the previous heating step.

[0067] In some cases, it may be preferable to carry out this step in an atmosphere containing water rather than a dry atmosphere. If an appropriate amount of water is present in the atmosphere, it may be possible to promote hydrolysis of fluorides such as magnesium fluoride. For this reason, for example, air may be used as the atmosphere in this step. Using air is preferable because it improves productivity. In addition, a mixture of air and oxygen gas may be used as the atmosphere in this step. Using a mixture of air and oxygen gas is preferable because it improves productivity while increasing the oxygen partial pressure.

[0068] If the particles of the mixture 903 stick to each other during heating, the distribution of the additives, which are preferably distributed near the surface, as described below, may deteriorate. In addition, the surface of the positive electrode active material, which is preferably smooth and has few irregularities, may become more irregular if the particles stick to each other, and defects such as cracks and fissures may increase. This is thought to be due to the fact that the adhesion of the mixture 903 to each other reduces the contact area with oxygen in the atmosphere and blocks the route for the additives to diffuse.

[0069] Therefore, by carrying out heating that has an effect of suppressing adhesion, a positive electrode active material having good characteristics can be produced. Heating may be carried out either continuously or batchwise.

[0070] Examples of heating that has an effect of suppressing adhesion include heating while stirring the mixture 903, heating while vibrating a container containing the mixture 903, and the like.

[0071] Heating in a rotary kiln can be performed while stirring, whether in a continuous or batch system, and is therefore preferred as adhesion suppression annealing. The continuous system is preferred because of its high productivity, while the batch system is preferred because of its easy atmosphere control.

[0072] When heating is performed using a roller hearth kiln, it is preferable to vibrate the container containing the mixture 903 during heating. The roller hearth kiln is a continuous type, and therefore has good productivity and is therefore preferable.

[0073] It is also preferable to put stirring balls or the like together with the mixture 903 into the rotary kiln or into a container containing the mixture 903. The material of the stirring balls is preferably one that is unlikely to react chemically with the mixture 903 or one that does not have a negative effect even if a chemical reaction occurs, and aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide, or the like is preferable. The adhesion suppression effect can be further strengthened by stirring the mixture 903 and the stirring balls together. It is preferable that the stirring balls are sufficiently larger than the particles of the positive electrode active material 100 so that they can be easily removed in a later process. However, if the stirring balls are too large, the stirring may not be performed sufficiently and the particle size of the positive electrode active material may become large. Therefore, it is preferable that the diameter of the stirring balls is, for example, 10 times or more and 100 times or less than the median diameter D50 of the positive electrode active material 100.

[0074] The heating temperature in step S43 must be equal to or higher than the temperature at which the reaction between LiMO2 and the mixture 902 proceeds. The temperature at which the reaction proceeds may be any temperature at which mutual diffusion of elements contained in LiMO2 and the mixture 902 occurs. Therefore, it may be lower than the melting temperature of these materials. For example, in the case of oxides, the melting temperature T m 0.757 times (Tammann temperature T d ) solid-state diffusion occurs. Therefore, for example, a temperature of 500°C or higher is sufficient.

[0075] However, the reaction proceeds more easily if the annealing temperature is equal to or higher than the temperature at which at least a part of the mixture 903 melts. Therefore, the annealing temperature is preferably equal to or higher than the eutectic point of the mixture 902. When the mixture 902 contains LiF and MgF2, the eutectic point of LiF and MgF2 is around 742°C, so it is preferable to set the temperature in step S43 to 742°C or higher.

[0076] In addition, in the mixture 903 in which LiCoO2:LiF:MgF2 is mixed to have a molar ratio of 100:0.33:1, an endothermic peak is observed near 830° C. in differential scanning calorimetry (DSC measurement). Therefore, when LiMO2 is lithium cobalt oxide, it is more preferable to set the temperature in step S43 to 830° C. or higher.

[0077] A higher annealing temperature is preferable because the reaction proceeds more easily, the annealing time is shorter, and the productivity is high.

[0078] However, the annealing temperature must be below the decomposition temperature of LiMO2 (1130°C for LiCoO2). At temperatures close to the decomposition temperature, there is concern that LiMO2 may decompose, albeit in small amounts. Therefore, the annealing temperature is preferably 1130°C or lower, more preferably 1000°C or lower, even more preferably 950°C or lower, and even more preferably 900°C or lower.

[0079] Therefore, the annealing temperature is preferably 500°C to 1130°C, more preferably 500°C to 1000°C, even more preferably 500°C to 950°C, and even more preferably 500°C to 900°C. Also, it is preferably 742°C to 1130°C, more preferably 742°C to 1000°C, even more preferably 742°C to 950°C, and even more preferably 742°C to 900°C. Also, it is preferably 830°C to 1130°C, more preferably 830°C to 1000°C, even more preferably 830°C to 950°C, and even more preferably 830°C to 900°C.

[0080] Furthermore, when the mixture 903 is heated, it is preferable to control the partial pressure of fluorine or fluoride in the atmosphere within an appropriate range.

[0081] In the manufacturing method described in this embodiment, some materials, for example, lithium fluoride, which is a fluorine source, function as a flux. This function makes it possible to lower the annealing temperature below the decomposition temperature of LiMO2, for example, to between 742°C and 950°C, and it is believed that additives such as magnesium can be distributed evenly near the surface, making it possible to manufacture a positive electrode active material with good characteristics.

[0082] However, because gaseous lithium fluoride is lighter than oxygen, when lithium fluoride volatilizes due to heating, the amount of lithium fluoride in mixture 903 decreases. This weakens its function as a flux. Therefore, it is necessary to heat while suppressing the volatilization of lithium fluoride. Even if lithium fluoride is not used as a fluorine source, the lithium on the LiMO2 surface may react with fluorine to produce lithium fluoride, which may then volatilize. Therefore, even if a fluoride with a higher melting point than lithium fluoride is used, it is still necessary to suppress volatilization in the same way.

[0083] Therefore, it is preferable to heat the mixture 903 in an atmosphere containing lithium fluoride, that is, to heat the mixture 903 in a state where the partial pressure of lithium fluoride is high in the heating furnace. By such heating, it is possible to suppress the volatilization of lithium fluoride in the mixture 903.

[0084] When heating using a rotary kiln, it is preferable to control the flow rate of the oxygen-containing atmosphere in the kiln to heat the mixture 903. For example, it is preferable to reduce the flow rate of the oxygen-containing atmosphere, to first purge the atmosphere and then not flow the atmosphere after introducing the oxygen atmosphere into the kiln, etc.

[0085] When heating is performed using a roller hearth kiln, the mixture 903 can be heated in an atmosphere containing lithium fluoride by, for example, placing a lid on a container containing the mixture 903.

[0086] The annealing is preferably performed for an appropriate time. The appropriate annealing time varies depending on conditions such as the annealing temperature, the size and composition of the LiMO2 in step S14, etc. If the particles are small, a lower temperature or a shorter time may be more preferable than if the particles are large.

[0087] For example, when the median diameter (D50) of the particles in step S14 is about 12 μm, the annealing temperature is preferably, for example, 600° C. or more and 950° C. or less. The annealing time is, for example, preferably 3 hours or more, more preferably 10 hours or more, and even more preferably 60 hours or more.

[0088] On the other hand, when the median diameter (D50) of the particles in step S24 is about 5 μm, the annealing temperature is preferably, for example, from 600° C. to 950° C. The annealing time is preferably, for example, from 1 hour to 10 hours, and more preferably about 2 hours.

[0089] The shorter the annealing time is within a range that does not impair the battery characteristics, the higher the productivity is, and therefore it is preferable.

[0090] The temperature drop time after annealing is preferably, for example, 10 hours or more and 50 hours or less.

[0091] <Step S44> Next, in step S44, the material that has been subjected to the adhesion suppression annealing can be recovered to produce the positive electrode active material 100. At this time, it is preferable to further sieve the recovered positive electrode active material 100.

[0092] 1, a manufacturing method in which adhesion suppression annealing is performed as step S43 has been described, but one embodiment of the present invention is not limited thereto. The adhesion of the workpiece can also be suppressed by a method as shown in steps S53 to S55 of FIG. 2 and FIG. 4. Since there are many common parts with FIG. 1, the different parts will be mainly described. For the common parts, the description of FIG. 1 can be referred to.

[0093] <Step S53> In step S53 in Fig. 2 and Fig. 4, the mixture 903 is heated in an atmosphere containing oxygen. At this time, stirring or the like is not particularly required. Other conditions can be taken into consideration as described in step S43. The mixture 903 heated at least once is referred to as a composite oxide.

[0094] <Step S54> Next, in step S54, the composite oxide is subjected to an adhesion suppression operation. Examples of the adhesion suppression operation of the composite oxide include crushing with a pestle, mixing with a ball mill, mixing with a rotating mixer, sieving, and vibrating a container containing the composite oxide. This process may also be preferably performed in an atmosphere containing water rather than a dry atmosphere. If an appropriate amount of water is present in the atmosphere, hydrolysis of fluorides such as magnesium fluoride may be promoted. Therefore, for example, air may be used as the atmosphere in this process. Using air is preferable because of its good productivity. Also, air and oxygen gas may be mixed and used as the atmosphere in this process. Using air and oxygen gas as a mixture is preferable because it improves productivity and increases the oxygen partial pressure.

[0095] <Step S55> Next, in step S55, the composite oxide after the adhesion suppression operation is heated in an atmosphere containing oxygen. The heating conditions can be taken into consideration in the description of step S53.

[0096] Step S54 and step S55 can be performed n times (n is an integer of 1 or more). If n is too large, the productivity decreases and the characteristics of the positive electrode active material may also deteriorate, which is not preferable. Therefore, for example, n is preferably 1 or more and 3 or less, and more preferably 2.

[0097] As in steps S53 to S55, adhesion of the composite oxide can be suppressed by performing an adhesion suppression operation between multiple heating steps. This method does not require stirring during heating, so adhesion can be suppressed even in a batch-type non-rotating furnace.

[0098] 1, the LiMO2 obtained in step S14 is mixed with the mixture 902 in step S41, but the present invention is not limited to this. As shown in steps S31, S32, and S41 in FIG. 3 and FIG. 4, other additives may be further mixed.

[0099] As the additive, for example, one or more selected from nickel, aluminum, manganese, titanium, zirconium, vanadium, iron, chromium, niobium, cobalt, arsenic, zinc, silicon, sulfur, phosphorus, and boron can be used. Figures 3 and 4 show an example in which two types of additives are used: a nickel source in step S31 and an aluminum source in step S32.

[0100] It is preferable to use these additives in the form of finely pulverized oxides, hydroxides, fluorides, etc. of the respective elements. The fine pulverization can be carried out, for example, by a wet method.

[0101] In this way, by separating the steps of introducing the transition metal M and the additive, the depth profile of each element may be changed. For example, the concentration of the additive may be increased near the surface compared to the inside of the positive electrode active material 100. In addition, the ratio of the number of atoms of the additive element to the number of atoms of the transition metal M as a standard may be made higher near the surface than in the inside.

[0102] This embodiment mode can be used in combination with other embodiment modes.

[0103] (Embodiment 2) In this embodiment, a positive electrode active material of one embodiment of the present invention will be described with reference to FIGS.

[0104] Fig. 5A is a top view of a positive electrode active material 100 according to one embodiment of the present invention. A cross-sectional view taken along line AB in Fig. 5A is shown in Fig. 5B.

[0105] <Elements and distribution> The positive electrode active material 100 contains lithium, a transition metal M, oxygen, and an additive. The positive electrode active material 100 may be said to be a composite oxide represented by LiMO2 to which the additive has been added.

[0106] As the transition metal M of the positive electrode active material 100, it is preferable to use a metal that can form a layered rock salt type composite oxide belonging to the space group R-3m together with lithium. For example, at least one of manganese, cobalt, and nickel can be used. That is, as the transition metal of the positive electrode active material 100, only cobalt may be used, only nickel may be used, two kinds of cobalt and manganese, two kinds of cobalt and nickel may be used, or three kinds of cobalt, manganese, and nickel may be used. That is, the positive electrode active material 100 can have a composite oxide containing lithium and the transition metal M, such as lithium cobalt oxide, lithium nickel oxide, lithium cobalt oxide in which a part of cobalt is replaced with manganese, lithium cobalt oxide in which a part of cobalt is replaced with nickel, and nickel-manganese-lithium cobalt oxide. If nickel is used as the transition metal M in addition to cobalt, the crystal structure may become more stable in a charged state at a high voltage, which is preferable.

[0107] As the additives contained in the positive electrode active material 100, it is preferable to use at least one of magnesium, fluorine, aluminum, titanium, zirconium, vanadium, iron, chromium, niobium, cobalt, arsenic, zinc, silicon, sulfur, phosphorus, and boron. These elements may further stabilize the crystal structure of the positive electrode active material 100, as described later. That is, the positive electrode active material 100 may have lithium cobalt oxide to which magnesium and fluorine have been added, lithium cobalt oxide to which magnesium, fluorine, and titanium have been added, lithium nickel-cobalt oxide to which magnesium and fluorine have been added, lithium cobalt-aluminate to which magnesium and fluorine have been added, lithium nickel-cobalt-aluminate, lithium nickel-cobalt-aluminate to which magnesium and fluorine have been added, lithium nickel-manganese-cobalt oxide to which magnesium and fluorine have been added, and the like. In this specification and the like, the term "additive" may be used instead of "mixture," "part of raw material," "impurity," and the like.

[0108] As shown in FIG. 5B, the positive electrode active material 100 has a surface layer 100a and an interior 100b. The surface layer 100a preferably has a higher concentration of additives than the interior 100b. As shown by the gradation in FIG. 5B, the additive preferably has a concentration gradient that increases from the interior toward the surface. In this specification and the like, the surface layer 100a refers to a region of the positive electrode active material 100 that is 10 nm or less in the depth direction from the surface. Surfaces caused by cracks or cracks may also be referred to as the surface. The region deeper than the surface layer 100a of the positive electrode active material 100 is referred to as the interior 100b.

[0109] In the positive electrode active material 100 of one embodiment of the present invention, even if lithium is released from the positive electrode active material 100 upon charging, the surface layer 100a, i.e., the outer periphery of the particle, having a high concentration of additives, reinforces the layered structure consisting of cobalt and oxygen octahedra so as not to be destroyed.

[0110] In addition, it is preferable that the concentration gradient of the additive is the same throughout the entire surface layer 100a of the positive electrode active material 100. It may be said that it is preferable that the reinforcement resulting from the high impurity concentration is present uniformly in the surface layer 100a. Even if a part of the surface layer 100a is reinforced, if there is a part without reinforcement, stress may be concentrated in the part without reinforcement, which is not preferable. If stress is concentrated in a part of the particle, defects such as cracks may occur there, which may lead to cracking of the positive electrode active material and a decrease in charge and discharge capacity.

[0111] Magnesium is divalent and is more stable at the lithium site than at the transition metal site in the layered rock-salt crystal structure, so it is more likely to enter the lithium site. The presence of magnesium at an appropriate concentration at the lithium site of the surface layer portion 100a makes it easier to maintain the layered rock-salt crystal structure. At an appropriate concentration, magnesium is preferable because it does not adversely affect the insertion and extraction of lithium associated with charging and discharging. However, if it is excessive, it may adversely affect the insertion and extraction of lithium. As described later, it is preferable that the concentration of the transition metal M in the surface layer portion 100a is higher than that of magnesium, for example.

[0112] Aluminum is trivalent and has a strong bond with oxygen. Therefore, by adding aluminum as an additive, the change in the crystal structure when it enters the lithium site can be suppressed. Therefore, it is possible to obtain a positive electrode active material 100 whose crystal structure is not easily destroyed even when the material is repeatedly charged and discharged.

[0113] Titanium oxide is known to have superhydrophilicity. Therefore, by making the surface layer 100a of the cathode active material 100 have titanium oxide, it is possible that the wettability with a highly polar solvent is improved. When used in a secondary battery, the cathode active material 100 has good contact at the interface with a highly polar electrolyte, which may suppress an increase in resistance.

[0114] As the charging voltage of a secondary battery increases, the voltage of the positive electrode generally increases. The positive electrode active material of one embodiment of the present invention has a stable crystal structure even at high voltages. Since the crystal structure of the positive electrode active material is stable in a charged state, the decrease in capacity due to repeated charging and discharging can be suppressed.

[0115] Moreover, a short circuit in a secondary battery not only causes problems in the charging and discharging operations of the secondary battery, but may also lead to heat generation and fire. In order to realize a safe secondary battery, it is preferable that a short circuit current is suppressed even at a high charging voltage. The positive electrode active material 100 of one embodiment of the present invention suppresses a short circuit current even at a high charging voltage. Therefore, a secondary battery that achieves both high capacity and safety can be obtained.

[0116] A secondary battery using the positive electrode active material 100 according to one embodiment of the present invention preferably simultaneously satisfies high capacity, excellent charge / discharge cycle characteristics, and safety.

[0117] The concentration gradient of the additive can be evaluated, for example, using energy dispersive X-ray spectroscopy (EDX). Among EDX measurements, EDX area analysis is performed by scanning an area and evaluating the area in two dimensions. Line analysis is performed by scanning linearly and evaluating the distribution of atomic concentration within the positive electrode active material particles. Line analysis may also be used to extract data for a linear area from EDX area analysis. Point analysis is used to measure an area without scanning it.

[0118] EDX surface analysis (e.g., element mapping) can quantitatively analyze the concentration of the additive in the surface layer 100a, the inside 100b, and the vicinity of the grain boundaries of the positive electrode active material 100. In addition, EDX line analysis can analyze the concentration distribution of the additive.

[0119] When EDX line analysis is performed on the positive electrode active material 100, the peak of the magnesium concentration in the surface layer 100a is preferably present at a depth of up to 3 nm from the surface of the positive electrode active material 100 toward the center, more preferably at a depth of up to 1 nm, and even more preferably at a depth of up to 0.5 nm.

[0120] In the present specification, the surface of the positive electrode active material 100 in the EDX analysis is estimated as the surface of the positive electrode active material 100 by calculating the average value of the detected amount of the interior 100b for elements present in the entire positive electrode active material 100, including cobalt and oxygen, and estimating the measurement point showing the measurement value closest to 50% of the average value. It is preferable to calculate the average value after subtracting the background. Cobalt is suitable for estimating the position of the surface because it is difficult to be included in the background and the average value of the interior 100b can be easily calculated. In addition, since the positive electrode active material 100 is a complex oxide, it is also suitable to use the detected amount of oxygen to estimate the surface.

[0121] In addition, the distribution of fluorine in the positive electrode active material 100 preferably overlaps with the distribution of magnesium. Therefore, when EDX analysis is performed, the peak of the fluorine concentration in the surface layer 100a is preferably present at a depth of up to 3 nm from the surface of the positive electrode active material 100 toward the center, more preferably at a depth of up to 1 nm, and even more preferably at a depth of up to 0.5 nm.

[0122] It is not necessary that all additives have the same concentration distribution. For example, when the positive electrode active material 100 has aluminum as an additive, it is preferable that the distribution is slightly different from that of magnesium and fluorine. For example, when EDX analysis is performed, it is preferable that the magnesium concentration peak is closer to the surface than the aluminum concentration peak of the surface layer 100a. For example, the aluminum concentration peak is preferably present at a depth of 0.5 nm to 20 nm from the surface of the positive electrode active material 100 toward the center, and more preferably at a depth of 1 nm to 5 nm.

[0123] When the positive electrode active material 100 is subjected to linear or area analysis, the ratio of the number of atoms of the impurity I to the transition metal M in the surface layer 100a (I / M) is preferably 0.05 to 1.00. When the impurity is titanium, the ratio of the number of atoms of the titanium to the transition metal M (Ti / M) is preferably 0.05 to 0.4, more preferably 0.1 to 0.3. When the impurity is magnesium, the ratio of the number of atoms of the magnesium to the transition metal M (Mg / M) is preferably 0.4 to 1.5, more preferably 0.45 to 1.00. When the impurity is fluorine, the ratio of the number of atoms of the fluorine to the transition metal M (F / M) is preferably 0.05 to 1.5, more preferably 0.3 to 1.00.

[0124] Furthermore, when the positive electrode active material 100 is subjected to a line analysis or an area analysis, the ratio (I / M) of the number of atoms of the additive I to the transition metal M in the vicinity of the crystal grain boundary is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. Even more preferably, it is 0.030 or more and 0.20 or less. For example, when the additive is magnesium and the transition metal is cobalt, the ratio (Mg / Co) of the number of atoms of magnesium to cobalt is preferably 0.020 or more and 0.50 or less. Even more preferably, it is 0.025 or more and 0.30 or less. Even more preferably, it is 0.030 or more and 0.20 or less.

[0125] As described above, if the additives contained in the positive electrode active material 100 are excessive, they may adversely affect the insertion and extraction of lithium. In addition, when used as a secondary battery, they may cause an increase in resistance and a decrease in capacity. On the other hand, if the impurities are insufficient, they may not be distributed throughout the entire surface layer portion 100a, and the effect of maintaining the crystal structure may be insufficient. Thus, the additives need to be at an appropriate concentration in the positive electrode active material 100, but it is not easy to adjust the concentration.

[0126] Therefore, for example, the positive electrode active material 100 may have a region where the additive is unevenly distributed. Due to the presence of such a region, the excess additive is removed from the interior 100b, and the additive concentration in the interior 100b can be made appropriate. By making the additive concentration in the interior 100b appropriate, it is possible to suppress an increase in resistance and a decrease in capacity when the battery is made into a secondary battery. Being able to suppress an increase in the resistance of the secondary battery is an extremely preferable characteristic, particularly in high-rate charging and discharging.

[0127] Furthermore, in the positive electrode active material 100 having a region where the additive is unevenly distributed, it is permissible to mix an excess amount of the additive in the manufacturing process to some extent, which is preferable since it provides a wider margin in production.

[0128] In this specification and the like, uneven distribution refers to the concentration of an element in a certain region being different from that in other regions, and may also be referred to as segregation, precipitation, non-uniformity, bias, high concentration, low concentration, and the like.

[0129] <Crystal structure>

[0130] Materials with a layered rock-salt crystal structure, such as lithium cobalt oxide (LiCoO2), are known to have a high discharge capacity and are excellent as positive electrode active materials for secondary batteries. An example of a material with a layered rock-salt crystal structure is the composite oxide represented by LiMO2.

[0131] It is known that the strength of the Jahn-Teller effect in transition metal compounds varies depending on the number of electrons in the d orbital of the transition metal.

[0132] In compounds containing nickel, distortion may occur easily due to the Jahn-Teller effect. Therefore, when LiNiO2 is charged and discharged at high voltage, there is a concern that the crystal structure may collapse due to distortion. It is suggested that the influence of the Jahn-Teller effect is small in LiCoO2, and it may have better resistance to charging and discharging at high voltage, which is preferable.

[0133] The positive electrode active material will be described with reference to Fig. 6 and Fig. 7. In Fig. 6 and Fig. 7, the case where cobalt is used as the transition metal M contained in the positive electrode active material will be described.

[0134] <Conventional positive electrode active materials> The positive electrode active material shown in Fig. 7 is lithium cobalt oxide (LiCoO2) to which fluorine and magnesium are not added by the manufacturing method described later. As described in Non-Patent Documents 1 and 2, etc., the crystal structure of the lithium cobalt oxide shown in Fig. 7 changes depending on the charge depth.

[0135] As shown in Figure 7, lithium cobalt oxide at a charge depth of 0 (discharged state) has a region with a crystal structure of space group R-3m, where lithium occupies octahedral sites and there are three CoO2 layers in the unit cell. Therefore, this crystal structure is sometimes called an O3 type crystal structure. Note that a CoO2 layer refers to an octahedral structure in which cobalt is coordinated with six oxygen atoms, and the octahedral structure is continuous on a plane with edge sharing.

[0136] At a charge depth of 1, the crystal structure has the space group P-3m1, and there is one CoO2 layer in the unit cell. Therefore, this crystal structure is sometimes called the O1 type crystal structure.

[0137] Lithium cobalt oxide with a charge depth of 0.73 or more, typically 0.88, has a crystal structure of space group R-3m. This structure can be said to be a structure in which a CoO2 structure such as P-3m1(O1) and a LiCoO2 structure such as R-3m(O3) are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3 type crystal structure. In reality, the number of cobalt atoms per unit cell in the H1-3 type crystal structure is twice that of other structures. However, in FIG. 7 and other parts of this specification, the c-axis of the H1-3 type crystal structure is shown as half the unit cell in order to make it easier to compare with other structures.

[0138] As an example, as described in Non-Patent Document 3, the coordinates of cobalt and oxygen in the unit cell of the H1-3 type crystal structure can be expressed as Co(0,0,0.42150±0.00016), O1(0,0,0.27671±0.00045), and O2(0,0,0.11535±0.00045). O1 and O2 are oxygen atoms. Thus, the H1-3 type crystal structure is expressed by a unit cell using one cobalt and two oxygens. On the other hand, as described later, the O3' type crystal structure of one embodiment of the present invention is preferably expressed by a unit cell using one cobalt and one oxygen. This indicates that the symmetry between cobalt and oxygen is different in the case of the O3' structure and the H1-3 type structure, and the change from the O3 structure in the O3' structure is smaller than that in the H1-3 type structure. The unit cell that is more preferably used to represent the crystal structure of the positive electrode active material may be selected, for example, so that the goodness of fit (GOF) value is smaller in Rietveld analysis of XRD.

[0139] When lithium cobalt oxide is repeatedly charged at a high voltage of 4.6 V or higher based on the redox potential of lithium metal, or when it is repeatedly charged to a deep depth of charge of 0.8 or higher, and then discharged, it undergoes repeated changes in crystal structure (i.e., a non-equilibrium phase change) between the H1-3 crystal structure and the R-3m(O3) structure in the discharged state.

[0140] However, these two crystal structures have a large deviation in the CoO2 layer. As shown by the dotted line and arrow in Figure 7, in the H1-3 type crystal structure, the CoO2 layer is significantly deviated from R-3m(O3). Such a dynamic structural change can have a negative effect on the stability of the crystal structure.

[0141] Furthermore, the difference in volume is large: when compared per the same number of cobalt atoms, the difference in volume between the H1-3 crystal structure and the O3 crystal structure in the discharged state is more than 3.0%.

[0142] In addition, the H1-3 crystal structure, which has continuous CoO2 layers such as P-3m1(O1), is likely to be unstable.

[0143] As a result, the crystal structure of lithium cobalt oxide breaks down when it is repeatedly charged and discharged at high voltages. This break in the crystal structure causes a deterioration in cycle characteristics. This is thought to be because the break in the crystal structure reduces the number of sites where lithium can exist stably and makes it difficult to insert and remove lithium.

[0144] <Positive Electrode Active Material of One Embodiment of the Present Invention> ≪Inside≫ The positive electrode active material 100 of one embodiment of the present invention can reduce the displacement of the CoO2 layer during repeated charging and discharging at high voltage. Furthermore, the change in volume can be reduced. Therefore, the positive electrode active material of one embodiment of the present invention can achieve excellent cycle characteristics. In addition, the positive electrode active material of one embodiment of the present invention can have a stable crystal structure in a high-voltage charged state. Therefore, the positive electrode active material of one embodiment of the present invention may be less likely to cause a short circuit when a high-voltage charged state is maintained. In such a case, safety is further improved, which is preferable.

[0145] In the positive electrode active material of one embodiment of the present invention, the change in crystal structure and the difference in volume per the same number of transition metal atoms between a fully discharged state and a high-voltage charged state are small.

[0146] The crystal structure of the positive electrode active material 100 before and after charging and discharging is shown in FIG. 6. The positive electrode active material 100 is a composite oxide containing lithium, cobalt as a transition metal M, and oxygen. In addition to the above, it is preferable to contain magnesium as an additive. It is also preferable to contain a halogen such as fluorine or chlorine as an additive.

[0147] The crystal structure at a charge depth of 0 (discharged state) in FIG. 6 is the same as that in FIG. 7, R-3m (O3). On the other hand, when the positive electrode active material 100 is at a fully charged charge depth, it has a crystal structure different from the H1-3 type crystal structure. This structure is in the space group R-3m, and although it is not a spinel type crystal structure, ions of cobalt, magnesium, etc. occupy oxygen 6 coordination positions, and the arrangement of cations has a symmetry similar to that of the spinel type. The symmetry of the CoO2 layer in this structure is the same as that of the O3 type. Therefore, this structure is referred to as an O3' type crystal structure or a pseudo-spinel type crystal structure in this specification. Therefore, the O3' type crystal structure may be referred to as a pseudo-spinel type crystal structure. In the diagram of the O3' type crystal structure shown in FIG. 8, lithium is omitted in order to explain the symmetry of the cobalt atom and the symmetry of the oxygen atom, but in reality, for example, 20 atomic % or less of lithium is present between the CoO2 layers with respect to cobalt. In both the O3 type crystal structure and the O3' type crystal structure, magnesium is preferably present dilutely between the CoO2 layers, i.e., at the lithium sites, and halogen such as fluorine is preferably present randomly and dilutely at the oxygen sites.

[0148] In the O3' type crystal structure, a light element such as lithium may occupy the oxygen tetracoordination site, and in this case too, the arrangement of ions has a symmetry similar to that of the spinel type.

[0149] It can also be said that the O3' type crystal structure is a crystal structure similar to the CdCl2 type crystal structure, although it has random Li between the layers. This CdCl2 type-like crystal structure was observed when lithium nickel oxide was charged to a charge depth of 0.94 (Li 0.06 The crystal structure is close to that of lithium cobalt oxide (NiO2), but it is known that pure lithium cobalt oxide or layered rock salt type positive electrode active materials that contain a large amount of cobalt do not usually have this crystal structure.

[0150] In the positive electrode active material 100 according to one embodiment of the present invention, when a large amount of lithium is released during charging at a high voltage, the change in the crystal structure is suppressed more than in conventional positive electrode active materials. For example, as shown by the dotted line in FIG. 6, there is almost no displacement of the CoO2 layer in these crystal structures.

[0151] More specifically, the cathode active material 100 of one embodiment of the present invention has high structural stability even when the charging voltage is high. For example, in a conventional cathode active material, the H1-3 crystal structure is formed at a charging voltage of about 4.6 V based on the potential of lithium metal, but the cathode active material 100 of one embodiment of the present invention can maintain the R-3m(O3) crystal structure even at a charging voltage of about 4.6 V. Even at a higher charging voltage, for example, a voltage of about 4.65 V to 4.7 V based on the potential of lithium metal, the cathode active material 100 of one embodiment of the present invention can have the O3' crystal structure. When the charging voltage is further increased beyond 4.7 V, the H1-3 crystal may finally be observed in the cathode active material 100 of one embodiment of the present invention. In addition, even when the charging voltage is lower (for example, when the charging voltage is 4.5 V or more and less than 4.6 V based on the potential of lithium metal, the cathode active material 100 of one embodiment of the present invention may have the O3' crystal structure.

[0152] In addition, when graphite is used as the negative electrode active material in the secondary battery, the voltage of the secondary battery is lower than the above by the potential of the graphite. The potential of graphite is about 0.05 V to 0.2 V based on the potential of lithium metal. Therefore, even when the voltage of a secondary battery using graphite as the negative electrode active material is 4.3 V or more and 4.5 V or less, the positive electrode active material 100 of one embodiment of the present invention can maintain the R-3m(O3) crystal structure, and can also have the O3'-type crystal structure in a region where the charging voltage is further increased, for example, when the voltage of the secondary battery is more than 4.5 V and less than 4.6 V. Furthermore, when the charging voltage is lower, for example, when the voltage of the secondary battery is 4.2 V or more and less than 4.3 V, the positive electrode active material 100 of one embodiment of the present invention can have the O3'-type crystal structure in some cases.

[0153] Therefore, in the positive electrode active material 100 of one embodiment of the present invention, the crystal structure is not easily destroyed even when charging and discharging are repeated at a high voltage.

[0154] In addition, the O3' type crystal structure can be expressed by the coordinates of cobalt and oxygen in the unit cell being Co(0,0,0.5), O(0,0,x), within the range of 0.20≦x≦0.25.

[0155] Additives such as magnesium that exist randomly and dilutely between the CoO2 layers, i.e., at the lithium sites, have the effect of suppressing the displacement of the CoO2 layers during charging at a high voltage. Therefore, when magnesium exists between the CoO2 layers, the O3' type crystal structure is easily formed. Therefore, it is preferable that magnesium is distributed throughout the particles of the positive electrode active material 100 of one embodiment of the present invention. In order to distribute magnesium throughout the particles, it is preferable to perform a heat treatment in the manufacturing process of the positive electrode active material 100 of one embodiment of the present invention.

[0156] However, if the heat treatment temperature is too high, cation mixing occurs, increasing the possibility that additives, such as magnesium, will enter the cobalt site. Magnesium present in the cobalt site is ineffective in maintaining the R-3m structure during high-voltage charging. Furthermore, if the heat treatment temperature is too high, there are concerns that it may have adverse effects such as reducing cobalt to a divalent state and evaporating lithium.

[0157] Therefore, it is preferable to add a halogen compound such as a fluoride to the lithium cobalt oxide before the heat treatment for distributing magnesium throughout the particles. The addition of the fluoride causes a drop in the melting point of the lithium cobalt oxide. The drop in the melting point makes it easier to distribute magnesium throughout the particles at a temperature where cation mixing is unlikely to occur. Furthermore, the presence of a fluorine compound is expected to improve corrosion resistance against hydrofluoric acid produced by decomposition of the electrolyte.

[0158] If the magnesium concentration is increased above a desired value, the effect of stabilizing the crystal structure may be reduced. This is believed to be because magnesium enters the cobalt site in addition to the lithium site. The number of magnesium atoms in the positive electrode active material of one embodiment of the present invention is preferably 0.001 times or more and 0.1 times or less than the number of atoms of the transition metal M, more preferably greater than 0.01 and less than 0.04, and even more preferably about 0.02. The magnesium concentration shown here may be, for example, a value obtained by performing elemental analysis of the entire particle of the positive electrode active material using ICP-MS or the like, or may be based on the value of the raw material composition in the process of producing the positive electrode active material.

[0159] Lithium cobalt oxide may be added with one or more metals selected from nickel, aluminum, manganese, titanium, vanadium and chromium as a metal other than cobalt (hereinafter, metal Z), and it is particularly preferable to add one or more of nickel and aluminum. Manganese, titanium, vanadium and chromium may be stable and tend to take 4 valences, and may contribute greatly to structural stability. In the positive electrode active material of one embodiment of the present invention, for example, the crystal structure may become more stable in a charged state at a high voltage by adding metal Z. Here, in the positive electrode active material of one embodiment of the present invention, metal Z is preferably added at a concentration that does not significantly change the crystallinity of lithium cobalt oxide. For example, it is preferable that the amount is such that the above-mentioned Jahn-Teller effect or the like is not expressed.

[0160] As shown in the legend in Figure 6, transition metals such as nickel and manganese and aluminum are preferably present at the cobalt site, but may be partially present at the lithium site. Magnesium is preferably present at the lithium site. Oxygen may be partially substituted with fluorine.

[0161] As the magnesium concentration of the positive electrode active material of one embodiment of the present invention increases, the capacity of the positive electrode active material may decrease. For example, the cause of this may be that magnesium enters the lithium site, thereby reducing the amount of lithium that contributes to charging and discharging. In addition, excessive magnesium may generate magnesium compounds that do not contribute to charging and discharging. When the positive electrode active material of one embodiment of the present invention has nickel as the metal Z in addition to magnesium, the capacity per weight and per volume may be increased. When the positive electrode active material of one embodiment of the present invention has aluminum as the metal Z in addition to magnesium, the capacity per weight and per volume may be increased. When the positive electrode active material of one embodiment of the present invention has nickel and aluminum in addition to magnesium, the capacity per weight and per volume may be increased.

[0162] Hereinafter, the concentrations of elements such as magnesium and metal Z contained in the positive electrode active material of one embodiment of the present invention will be expressed in terms of the number of atoms.

[0163] The number of nickel atoms in the positive electrode active material according to one embodiment of the present invention is preferably 7.5% or less of the number of cobalt atoms, more preferably 0.05% to 4%, and more preferably 0.1% to 2%. The nickel concentration shown here may be a value obtained by performing elemental analysis of the entire particles of the positive electrode active material using ICP-MS or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.

[0164] The number of aluminum atoms in the positive electrode active material according to one embodiment of the present invention is preferably 0.05% to 4%, more preferably 0.1% to 2%, of the number of cobalt atoms. The aluminum concentration shown here may be a value obtained by performing elemental analysis of the entire particles of the positive electrode active material using ICP-MS or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.

[0165] The positive electrode active material of one embodiment of the present invention preferably contains an element X, and phosphorus is preferably used as the element X. Furthermore, the positive electrode active material of one embodiment of the present invention more preferably contains a compound containing phosphorus and oxygen.

[0166] When the positive electrode active material of one embodiment of the present invention contains a compound containing element X, a short circuit may be less likely to occur when the positive electrode active material is maintained in a charged state at a high voltage.

[0167] When the positive electrode active material of one embodiment of the present invention contains phosphorus as the element X, hydrogen fluoride generated by decomposition of the electrolyte may react with the phosphorus, resulting in a decrease in the hydrogen fluoride concentration in the electrolyte.

[0168] When the electrolyte contains LiPF6, hydrogen fluoride may be generated by hydrolysis. Hydrogen fluoride may also be generated by the reaction of PVDF, which is used as a component of the positive electrode, with an alkali. By reducing the hydrogen fluoride concentration in the electrolyte, corrosion of the current collector and peeling of the coating may be suppressed. In addition, it may be possible to suppress the decrease in adhesion due to gelation or insolubilization of PVDF.

[0169] When the positive electrode active material of one embodiment of the present invention has magnesium in addition to the element X, the stability in a high-voltage charged state is extremely high. When the element X is phosphorus, the number of phosphorus atoms is preferably 1% to 20% of the number of cobalt atoms, more preferably 2% to 10%, and even more preferably 3% to 8%, and the number of magnesium atoms is preferably 0.1% to 10% of the number of cobalt atoms, more preferably 0.5% to 5%, and even more preferably 0.7% to 4%. The concentrations of phosphorus and magnesium shown here may be values ​​obtained by performing elemental analysis of the entire particles of the positive electrode active material using, for example, ICP-MS or the like, or may be based on values ​​of the composition of raw materials in the process of producing the positive electrode active material.

[0170] When the positive electrode active material has cracks, the progression of the cracks may be inhibited by the presence of phosphorus, more specifically, a compound containing phosphorus and oxygen, inside the cracks.

[0171] ≪Surface layer≫ Magnesium is preferably distributed throughout the particle of the positive electrode active material 100 according to one embodiment of the present invention, and in addition, the magnesium concentration in the surface layer 100a is preferably higher than the average of the entire particle. For example, the magnesium concentration in the surface layer 100a measured by XPS or the like is preferably higher than the average magnesium concentration of the entire particle measured by ICP-MS or the like.

[0172] In addition, when the positive electrode active material 100 of one embodiment of the present invention contains an element other than cobalt, for example, one or more metals selected from nickel, aluminum, manganese, iron, and chromium, the concentration of the metal in the surface layer is preferably higher than the average concentration of the entire particle. For example, the concentration of the element other than cobalt in the surface layer 100a measured by XPS or the like is preferably higher than the average concentration of the element in the entire particle measured by ICP-MS or the like.

[0173] The particle surface is, so to speak, entirely made up of crystal defects, and since lithium is removed from the surface during charging, the lithium concentration is likely to be lower than in the interior. Therefore, the surface is prone to become unstable and the crystal structure is likely to collapse. If the magnesium concentration in the surface layer 100a is high, the change in the crystal structure can be more effectively suppressed. In addition, if the magnesium concentration in the surface layer 100a is high, it is expected that the corrosion resistance against hydrofluoric acid generated by decomposition of the electrolyte will be improved.

[0174] In addition, it is preferable that the concentration of fluorine or the like in the surface layer portion 100a of the positive electrode active material 100 according to one embodiment of the present invention is higher than the average concentration in the entire particle. The presence of fluorine in the surface layer portion 100a, which is the region in contact with the electrolyte, can effectively improve corrosion resistance to hydrofluoric acid.

[0175] In this manner, the surface layer portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably has a composition different from that of the inside, that is, the concentration of additives, for example, magnesium and fluorine, is higher than that of the inside 100b. In addition, the composition preferably has a stable crystal structure at room temperature. Therefore, the surface layer portion 100a may have a crystal structure different from that of the inside 100b. For example, at least a part of the surface layer portion 100a of the positive electrode active material 100 of one embodiment of the present invention may have a rock salt crystal structure. In addition, when the surface layer portion 100a and the inside 100b have different crystal structures, it is preferable that the crystal orientations of the surface layer portion 100a and the inside 100b are approximately the same.

[0176] However, if the surface layer 100a is only MgO or only a structure in which MgO and CoO(II) are solid-solved, it becomes difficult to insert and remove lithium. Therefore, the surface layer 100a must contain at least cobalt, and in the discharged state, it must also contain lithium, and must have a path for the insertion and removal of lithium. In addition, it is preferable that the concentration of cobalt is higher than that of magnesium.

[0177] Moreover, the element X is preferably located in the surface layer portion 100a of the particle of the positive electrode active material 100 of one embodiment of the present invention. For example, the positive electrode active material 100 of one embodiment of the present invention may be covered with a coating containing the element X.

[0178] ≪Grain boundary≫ The additive contained in the positive electrode active material 100 of one embodiment of the present invention may be present randomly and dilutely inside the positive electrode active material 100, but more preferably, a part of the additive is segregated at the grain boundaries.

[0179] In other words, the concentration of the additive at and near the grain boundaries of the positive electrode active material 100 of one embodiment of the present invention is also preferably higher than that in other internal regions.

[0180] Like the grain surface, the grain boundary is also a planar defect. Therefore, it is easily unstable and the crystal structure is easily changed. Therefore, if the concentration of additives at and near the grain boundary is high, the change in the crystal structure can be more effectively suppressed.

[0181] Furthermore, when the additive concentration is high at and near the grain boundary, even if cracks occur along the grain boundary of the particles of the positive electrode active material 100 of one embodiment of the present invention, the additive concentration is high near the surface caused by the cracks. Therefore, the corrosion resistance to hydrofluoric acid can be improved even in the positive electrode active material after the cracks occur.

[0182] In this specification and the like, the vicinity of a crystal grain boundary refers to a region within about 10 nm from the grain boundary.

[0183] ≪Particle size≫ If the particle size of the positive electrode active material 100 of one embodiment of the present invention is too large, problems such as difficulty in diffusing lithium and excessive roughness of the surface of the active material layer when applied to a current collector arise. On the other hand, if the particle size is too small, problems such as difficulty in supporting the active material layer when applied to a current collector and excessive reaction with an electrolyte solution arise. Therefore, the average particle size (D50: also referred to as median diameter) is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less.

[0184] <Analysis method> Whether or not a certain positive electrode active material is the positive electrode active material 100 of one embodiment of the present invention that exhibits an O3'-type crystal structure when charged at a high voltage can be determined by analyzing the positive electrode charged at a high voltage using XRD, electron beam diffraction, neutron beam diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. In particular, XRD is preferable in that it can analyze the symmetry of transition metals such as cobalt contained in the positive electrode active material with high resolution, it can compare the degree of crystallinity and the orientation of the crystals, it can analyze the periodic distortion of the lattice and the crystallite size, and it can obtain sufficient accuracy even if the positive electrode obtained by disassembling the secondary battery is measured as it is.

[0185] As described above, the positive electrode active material 100 according to one embodiment of the present invention is characterized by a small change in crystal structure between a high-voltage charged state and a discharged state. A material in which a crystal structure that changes significantly from a discharged state when charged at a high voltage accounts for 50 wt% or more is not preferable because it cannot withstand high-voltage charging and discharging. It is also important to note that the desired crystal structure may not be obtained by simply adding an additive element. For example, even if lithium cobalt oxide containing magnesium and fluorine is common, there are cases in which the O3'-type crystal structure accounts for 60 wt% or more when charged at a high voltage, and cases in which the H1-3-type crystal structure accounts for 50 wt% or more. In addition, at a certain voltage, the O3'-type crystal structure is almost 100 wt%, and when the certain voltage is further increased, the H1-3-type crystal structure may occur. Therefore, in order to determine whether or not a material is the positive electrode active material 100 according to one embodiment of the present invention, analysis of the crystal structure, including XRD, is required.

[0186] However, when the positive electrode active material is charged or discharged at a high voltage, its crystal structure may change when it comes into contact with the air. For example, it may change from an O3'-type crystal structure to an H1-3-type crystal structure. Therefore, it is preferable to handle all samples in an inert atmosphere such as an argon atmosphere.

[0187] ≪Charging method≫ High-voltage charging for determining whether a certain composite oxide is the positive electrode active material 100 of one embodiment of the present invention can be performed, for example, by preparing a coin cell (CR2032 type, diameter 20 mm, height 3.2 mm) with a lithium counter electrode and charging it.

[0188] More specifically, for the positive electrode, a slurry in which a positive electrode active material, a conductive additive, and a binder are mixed is applied to a positive electrode current collector made of aluminum foil and used.

[0189] Lithium metal can be used for the counter electrode. When a material other than lithium metal is used for the counter electrode, the potential of the secondary battery is different from the potential of the positive electrode. Unless otherwise specified, the voltage and potential in this specification are the potential of the positive electrode.

[0190] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6), and the electrolytic solution can be a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of EC:DEC = 3:7, with 2 wt% vinylene carbonate (VC).

[0191] The separator can be made of polypropylene having a thickness of 25 μm.

[0192] The positive electrode can and the negative electrode can may be made of stainless steel (SUS).

[0193] The coin cell prepared under the above conditions is charged at a constant current of 4.6 V and 0.5 C, and then charged at a constant voltage until the current value reaches 0.01 C. Here, 1 C is 137 mA / g. The temperature is 25°C. After charging in this manner, the coin cell is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out to obtain a positive electrode active material charged at a high voltage. When various analyses are performed after this, it is preferable to seal the cell in an argon atmosphere to suppress reactions with external components. For example, XRD can be performed by sealing the cell in an airtight container in an argon atmosphere.

[0194] <XRD> The XRD measurement apparatus and conditions are not particularly limited. For example, the measurement can be performed using the following apparatus and conditions. XRD equipment: Bruker AXS, D8 ADVANCE X-ray source:CuKα ray Output: 40KV, 40mA Slit type: Div.Slit, 0.5° Detector: LynxEye Scan method: 2θ / θ continuous scan Measurement range (2θ): 15° to 90° Step width (2θ): 0.01° setting Counting time: 1 second / step Sample stage rotation: 15 rpm

[0195] If the measurement sample is a powder, it can be set by placing it in a glass sample holder, sprinkling the sample on a greased silicone non-reflective plate, etc. If the measurement sample is a positive electrode, the positive electrode can be attached to the substrate with double-sided tape, and the positive electrode active material layer can be set to match the measurement surface required by the device.

[0196] Figure 8 shows an ideal powder XRD pattern using CuKα1 radiation calculated from the O3' type crystal structure and the H1-3 type crystal structure model. For comparison, ideal XRD patterns calculated from the crystal structures of LiCoO2(O3) at charge depth 0 and CoO2(O1) at charge depth 1 are also shown. The patterns of LiCoO2(O3) and CoO2(O1) were created using Reflex Powder Diffraction, one of the modules of Materials Studio (BIOVIA), from crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) (see Non-Patent Document 4). The 2θ range was 15° to 75°, Step size = 0.01, and wavelength λ1 = 1.540562 × 10 -10 m and λ2 were not set, and monochromator was set to single. The pattern of the H1-3 type crystal structure was similarly created from the crystal structure information described in Non-Patent Document 3. The pattern of the O3' type crystal structure was estimated from the XRD pattern of the positive electrode active material of one embodiment of the present invention, and fitted using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker), and an XRD pattern was created in the same manner as the others.

[0197] As shown in Figure 8, in the O3' type crystal structure, diffraction peaks appear at 2θ = 19.30 ± 0.20° (19.10° to 19.50°) and 2θ = 45.55 ± 0.10° (45.45° to 45.65°). More specifically, sharp diffraction peaks appear at 2θ = 19.30 ± 0.10° (19.20° to 19.40°) and 2θ = 45.55 ± 0.05° (45.50° to 45.60°). However, no peaks appear at these positions in the H1-3 type crystal structure and CoO2 (P-3m1, O1). Therefore, the appearance of peaks at 2θ=19.30±0.20° and 2θ=45.55±0.10° in a state charged at a high voltage can be said to be a characteristic of the positive electrode active material 100 of one embodiment of the present invention.

[0198] This can also be said to be because the positions at which the XRD diffraction peaks appear are close between the crystal structure at a charge depth of 0 and the crystal structure when charged at a high voltage. More specifically, the difference in the positions at which the peaks appear for two or more, more preferably three or more, of the main diffraction peaks of both structures is 2θ=0.7 or less, more preferably 2θ=0.5 or less.

[0199] Note that the positive electrode active material 100 of one embodiment of the present invention has an O3'-type crystal structure when charged at a high voltage, but not all of the particles may have an O3'-type crystal structure. Other crystal structures may be included, or a part may be amorphous. However, when Rietveld analysis is performed on the XRD pattern, the O3'-type crystal structure is preferably 50 wt% or more, more preferably 60 wt% or more, and even more preferably 66 wt% or more. When the O3'-type crystal structure is 50 wt% or more, more preferably 60 wt% or more, and even more preferably 66 wt% or more, the positive electrode active material can have sufficiently excellent cycle characteristics.

[0200] Furthermore, even after 100 or more charge / discharge cycles from the start of measurement, when Rietveld analysis is performed, the O3' type crystal structure is preferably 35 wt% or more, more preferably 40 wt% or more, and even more preferably 43 wt% or more.

[0201] In addition, the crystallite size of the O3' type crystal structure of the positive electrode active material particles only decreases to about 1 / 10 of that of LiCoO2(O3) in the discharged state. Therefore, even under the same XRD measurement conditions as the positive electrode before charging and discharging, a clear peak of the O3' type crystal structure can be confirmed after high-voltage charging. On the other hand, in the case of simple LiCoO2, even if some of it can take on a structure similar to the O3' type crystal structure, the crystallite size becomes smaller and the peak becomes broad and small. The crystallite size can be calculated from the half-width of the XRD peak.

[0202] As described above, the positive electrode active material of one embodiment of the present invention is preferably small in influence of the Jahn-Teller effect. The positive electrode active material of one embodiment of the present invention preferably has a layered rock salt type crystal structure and mainly contains cobalt as a transition metal. In addition, the positive electrode active material of one embodiment of the present invention may contain the above-mentioned metal Z in addition to cobalt, as long as the influence of the Jahn-Teller effect is small.

[0203] In the positive electrode active material, the range of lattice constants in which the influence of the Jahn-Teller effect is small is considered using XRD analysis.

[0204] FIG. 9 shows the results of estimating the a-axis and c-axis lattice constants by XRD when the positive electrode active material of one embodiment of the present invention has a layered rock-salt crystal structure and contains cobalt and nickel. FIG. 9A shows the result for the a-axis, and FIG. 9B shows the result for the c-axis. Note that FIG. 9 shows the XRD pattern of the powder after the synthesis of the positive electrode active material, which is before being incorporated into the positive electrode. The nickel concentration on the horizontal axis indicates the nickel concentration when the sum of the number of atoms of cobalt and nickel is 100%. The positive electrode active material was prepared by steps S21 to S25 described later, and a cobalt source and a nickel source were used in step S21. The nickel concentration indicates the nickel concentration when the sum of the number of atoms of cobalt and nickel is 100% in step S21.

[0205] FIG. 10 shows the results of estimating the lattice constants of the a-axis and c-axis by XRD when the positive electrode active material of one embodiment of the present invention has a layered rock-salt crystal structure and contains cobalt and manganese. FIG. 10A shows the result for the a-axis, and FIG. 10B shows the result for the c-axis. Note that FIG. 10 shows the XRD pattern of the powder after the synthesis of the positive electrode active material, which is before being incorporated into the positive electrode. The manganese concentration on the horizontal axis indicates the concentration of manganese when the sum of the number of atoms of cobalt and manganese is 100%. The positive electrode active material was prepared by steps S21 to S25 described later, and a cobalt source and a manganese source were used in step S21. The manganese concentration indicates the concentration of manganese when the sum of the number of atoms of cobalt and manganese is 100% in step S21.

[0206] Figure 9C shows the value obtained by dividing the a-axis lattice constant by the c-axis lattice constant (a-axis / c-axis) for the positive electrode active materials whose lattice constant results are shown in Figures 9A and 9B. Figure 10C shows the value obtained by dividing the a-axis lattice constant by the c-axis lattice constant (a-axis / c-axis) for the positive electrode active materials whose lattice constant results are shown in Figures 10A and 10B.

[0207] From Figure 9C, it can be seen that when the nickel concentration is 5% or 7.5%, the a-axis / c-axis tends to change significantly, and the distortion of the a-axis is considered to be large. This distortion may be Jahn-Teller distortion. It is suggested that an excellent positive electrode active material with small Jahn-Teller distortion can be obtained when the nickel concentration is less than 7.5%.

[0208] Next, Fig. 10A suggests that when the manganese concentration is 5% or more, the behavior of the change in lattice constant is different and does not follow Vegard's law. Therefore, it is suggested that when the manganese concentration is 5% or more, the crystal structure is different. Therefore, the manganese concentration is preferably, for example, 4% or less.

[0209] The above ranges of nickel concentration and manganese concentration do not necessarily apply to the surface layer 100a of the particle, that is, the concentrations in the surface layer 100a of the particle may be higher than the above ranges.

[0210] As a result of considering the above-mentioned preferable range of the lattice constant, it was found that in the positive electrode active material of one embodiment of the present invention, the lattice constant of the a-axis is 2.814 × 10 in the layered rock-salt crystal structure of the particles of the positive electrode active material in a state where no charge / discharge is performed or in a discharged state, which can be estimated from the XRD pattern. -10 m or larger, 2.817×10 -10 m and the c-axis lattice constant is 14.05×10 -10 m or larger, 14.07×10 -10 It has been found that the value is preferably smaller than m. The state in which charging and discharging are not performed may be, for example, the powder state prior to fabrication of the positive electrode of a secondary battery.

[0211] Alternatively, in the layered rock-salt crystal structure possessed by the particles of the positive electrode active material in a state where no charge or discharge is performed or in a discharged state, it is preferable that the value obtained by dividing the lattice constant of the a-axis by the lattice constant of the c-axis (a-axis / c-axis) is greater than 0.20000 and smaller than 0.20049.

[0212] Alternatively, in the layered rock-salt crystal structure of particles of a positive electrode active material in a state where no charge or discharge is performed or in a discharged state, when XRD analysis is performed, a first peak may be observed at 2θ of 18.50° or more and 19.30° or less, and a second peak may be observed at 2θ of 38.00° or more and 38.80° or less.

[0213] The peaks appearing in the powder XRD pattern reflect the crystal structure of the interior 100b of the positive electrode active material 100, which occupies most of the volume of the positive electrode active material 100. The crystal structure of the surface layer 100a, etc. can be analyzed by electron beam diffraction of a cross section of the positive electrode active material 100, etc.

[0214] <XPS> X-ray photoelectron spectroscopy (XPS) can analyze a region from the surface to a depth of about 2 to 8 nm (usually about 5 nm), so the concentration of each element can be quantitatively analyzed for about half of the depth direction of the surface layer 100a. In addition, narrow scan analysis can analyze the bonding state of the elements. The quantitative accuracy of XPS is often about ±1 atomic %, and the lower detection limit is about 1 atomic %, depending on the element.

[0215] When the positive electrode active material 100 according to one embodiment of the present invention is subjected to XPS analysis, the number of atoms of the additive is preferably 1.6 to 6.0 times, more preferably 1.8 to less than 4.0 times, the number of atoms of the transition metal M. When the additive is magnesium and the transition metal M is cobalt, the number of magnesium atoms is preferably 1.6 to 6.0 times, more preferably 1.8 to less than 4.0 times, the number of cobalt atoms. The number of fluorine atoms is preferably 0.2 to 6.0 times, more preferably 1.2 to 4.0 times, the number of atoms of the transition metal M.

[0216] When performing XPS analysis, for example, monochromated aluminum can be used as the X-ray source, and the take-off angle can be set to, for example, 45°.

[0217] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, the peak showing the bond energy between fluorine and other elements is preferably 682 eV or more and less than 685 eV, and more preferably about 684.3 eV. This value is different from both the bond energy of lithium fluoride, 685 eV, and the bond energy of magnesium fluoride, 686 eV. In other words, when the positive electrode active material 100 of one embodiment of the present invention contains fluorine, the bond is preferably other than that of lithium fluoride and magnesium fluoride.

[0218] Furthermore, when the positive electrode active material 100 of one embodiment of the present invention is subjected to XPS analysis, the peak showing the bond energy between magnesium and another element is preferably equal to or greater than 1302 eV and less than 1304 eV, and more preferably about 1303 eV. This value is different from the bond energy of magnesium fluoride, 1305 eV, and is close to the bond energy of magnesium oxide. In other words, when the positive electrode active material 100 of one embodiment of the present invention contains magnesium, the bond is preferably other than that of magnesium fluoride.

[0219] Additives that are preferably present in large amounts in the surface layer 100a, such as magnesium and aluminum, preferably have concentrations measured by XPS or the like that are higher than the concentrations measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry) or the like.

[0220] When a cross section of magnesium or aluminum is exposed by processing and the cross section is analyzed by TEM-EDX, it is preferable that the concentration of the surface layer 100a is higher than the concentration of the inside 100b. The processing can be performed by, for example, FIB (Focused Ion Beam).

[0221] In XPS (X-ray photoelectron spectroscopy) analysis, the number of magnesium atoms is preferably 0.4 to 1.5 times the number of cobalt atoms, while the ratio of the number of magnesium atoms Mg / Co in ICP-MS analysis is preferably 0.001 to 0.06.

[0222] On the other hand, it is preferable that nickel contained in the transition metal M is not unevenly distributed in the surface layer portion 100a, but is distributed throughout the positive electrode active material 100. However, this is not the case when there is a region where the excess additive is unevenly distributed as described above.

[0223] <Surface roughness and specific surface area> The positive electrode active material 100 according to one embodiment of the present invention preferably has a smooth surface with few irregularities. A smooth surface with few irregularities is one factor indicating that the additive is well distributed in the surface layer portion 100a.

[0224] Whether the surface is smooth and has few projections and recesses can be determined, for example, from a cross-sectional SEM image or cross-sectional TEM image of the positive electrode active material 100, the specific surface area of ​​the positive electrode active material 100, or the like.

[0225] For example, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 as follows.

[0226] First, the cathode active material 100 is processed by FIB or the like to expose the cross section. At this time, it is preferable to cover the cathode active material 100 with a protective film, a protective agent, or the like. Next, an SEM image of the interface between the protective film or the like and the cathode active material 100 is taken. The SEM image is subjected to noise processing using image processing software. For example, Gaussian blurring (σ=2) is performed, and then binarization is performed. Furthermore, interface extraction is performed using image processing software. Furthermore, the interface line between the protective film or the like and the cathode active material 100 is selected using an automatic selection tool or the like, and data is extracted to a spreadsheet software or the like. Using the functions of the spreadsheet software or the like, correction is performed from the regression curve (quadratic regression), and a parameter for calculating roughness is obtained from the data after the slope correction, and the root mean square surface roughness (RMS) is obtained by calculating the standard deviation. In addition, this surface roughness is the surface roughness at least at 400 nm of the outer periphery of the particle of the cathode active material.

[0227] The particle surfaces of the positive electrode active material 100 of this embodiment preferably have a roughness index (RMS: root mean square surface roughness) of less than 3 nm, preferably less than 1 nm, and more preferably less than 0.5 nm.

[0228] The image processing software used for noise processing, boundary extraction, etc. is not particularly limited, but for example, "ImageJ" can be used. The spreadsheet software is also not particularly limited, but for example, Microsoft Office Excel can be used.

[0229] For example, the actual specific surface area A measured by the constant volume gas adsorption method R and the ideal specific surface area A i The smoothness of the surface of the positive electrode active material 100 can also be expressed as a numerical value based on the ratio of the surface smoothness to the surface smoothness.

[0230] Ideal specific surface area A i is calculated assuming that all particles have the same diameter, the same weight, and an ideal spherical shape.

[0231] The median diameter D50 can be measured by a particle size distribution meter using a laser diffraction / scattering method, etc. The specific surface area can be measured by a specific surface area measuring device using a gas adsorption method by a constant volume method, for example.

[0232] The positive electrode active material 100 according to one embodiment of the present invention has an ideal specific surface area A calculated from the median diameter D50. i and the actual specific surface area A R Ratio of A R / A i It is preferable that the ratio is 2 or less.

[0233] This embodiment can be used in combination with other embodiment modes.

[0234] (Embodiment 3) In this embodiment, a manufacturing apparatus according to one embodiment of the present invention will be described with reference to Fig. 11 to Fig. 14. The manufacturing apparatus is suitable for manufacturing the positive electrode active material described in the previous embodiment.

[0235] <Batch type rotary kiln> 11A shows a schematic cross-sectional view of a batch-type rotary kiln 110. The rotary kiln 110 has a kiln body 111, a heating means 112, a raw material supplying means 113, and an atmosphere control means 116. The rotary kiln 110 also preferably has a control panel 115 and a measuring device 120.

[0236] The kiln body 111 is substantially cylindrical, with one end connected to a raw material supply means 113 and the other end having a discharge section 114. The material to be treated that is placed inside the kiln is agitated by the rotation of the kiln body.

[0237] The heating means 112 has a function of heating the kiln body 111 to a temperature of 700° C. to 1200° C. As the heating means, for example, a silicon carbide heater, a carbon heater, a metal heater, a molybdenum disilicide heater, or the like can be used.

[0238] The raw material supplying means 113 has a function of feeding the material to be treated into the kiln body 111 .

[0239] The atmosphere control means 116 has a function of controlling the atmosphere inside the kiln body 111. An example of the atmosphere control means 116 is a gas introduction line. The gas to be introduced preferably contains oxygen.

[0240] The control panel 115 can control the heating temperature, atmosphere, etc. of the kiln body 111.

[0241] The measuring device 120 can measure, for example, the atmosphere inside the kiln body 111. As the measuring device 120, GC (gas chromatography), MS (mass spectrometer), GC-MS, IR (infrared spectroscopy), FT-IR (Fourier transform infrared spectroscopy), etc. can be applied. By measuring the atmosphere of the kiln body 111, more specifically, the partial pressure of lithium fluoride, oxygen, etc., it is possible to confirm whether the heating conditions are favorable. Note that the measuring device 120 may be a measuring device other than the atmosphere, as long as it can confirm that the heating conditions are favorable. For example, a quartz crystal vibration type film thickness meter or the like may be provided as the measuring device 120 at or near the exhaust port. The discharged lithium fluoride is cooled and accumulated at or near the exhaust port. Therefore, the lithium fluoride can be quantitatively measured by measuring the film thickness with a quartz crystal vibration type film thickness meter.

[0242] In the rotary kiln 110, the material to be treated can be agitated by rotating the kiln body 111 during heating, so that particles of the material to be treated are less likely to stick to each other. In other words, the process of rotating the kiln body 111 is the sticking prevention process.

[0243] The batch method as shown in FIG. 11A is preferable because it is easy to control the atmosphere.

[0244] 11B and 11C, a rotary kiln 110a may be used having a kiln body 111a with an internal stirring blade 117. Fig. 11B is a schematic cross-sectional view of a batch-type rotary kiln 110a, and Fig. 11C is a cross-sectional view of the kiln body 111a taken along line A-A' in Fig. 11B.

[0245] 11B and 11C show an example of a kiln body 111a having one straight blade 117, but this is not a limitation of one embodiment of the present invention. A plurality of blades 117 may be provided. The blade 117 may also have another shape, such as a spiral shape.

[0246] <Continuous rotary kiln> The rotary kiln is not limited to a batch type, and may be a continuous type. It may have a plurality of raw material supply means and a function of supplying new raw materials during heating. It may also have a mill inside the kiln body, which prevents the workpiece from sticking.

[0247] 12A shows a schematic cross-sectional view of a continuous rotary kiln 110b having multiple raw material supply means and a mill. The rotary kiln 110b has a kiln body 111, heating means 112a and 112b, raw material supply means 113a and 113b, and atmosphere control means 116. The rotary kiln 110b also preferably has a control panel 115 and a measuring device 120.

[0248] The kiln body 111 is substantially cylindrical, with a raw material supply means 113a connected to one end and a discharge section 114 at the other end, with raw material supply means 113b connected between them. The section from the raw material supply means 113a to just before the raw material supply means 113b is referred to as the upstream section. The section from the raw material supply means 113b to the discharge section 114 is referred to as the downstream section. It is also preferable that a mill 130 is provided inside the kiln body 111.

[0249] The kiln body 111 preferably has a function of retaining the material to be treated for 1 hour or more and 100 hours or less in the upstream portion, and preferably has a function of retaining the material to be treated for 1 hour or more and 100 hours or less in the downstream portion.

[0250] The raw material supplying means 113a has a function of supplying the material to be treated to the upstream portion of the kiln body 111. The raw material supplying means 113b has a function of supplying additional raw material to the downstream portion of the kiln body 111.

[0251] The mill 130 has a function of suppressing adhesion of the workpiece. Specifically, the workpiece passes between the mill 130 and the inner wall of the kiln body 111 as shown by the dotted arrow in the figure, thereby suppressing adhesion. Note that, although one mill 130 is provided in the upstream portion in FIG. 12A, one embodiment of the present invention is not limited to this. A plurality of mills 130 may be provided. Also, one mill may be provided in the downstream portion, or one mill may be provided in both the upstream portion and the downstream portion.

[0252] The heating means 112a and the heating means 112b can be set to different heating temperatures. For example, the heating means 112a for heating the upstream portion preferably has a function of heating to 800°C or more and 1200°C or less. The heating means 112b for heating the downstream portion preferably has a function of heating to 700°C or more and 1000°C or less. The portion where the mill 130 is provided may be at a temperature lower than the above-mentioned temperatures.

[0253] For the atmosphere control means 116, the control panel 115, the measuring device 120, etc., the description of FIG. 11A can be referred to.

[0254] A continuous rotary kiln is preferable because it is easy to improve productivity. By using the rotary kiln 110b configured as described above, a positive electrode active material with better performance can be produced with good productivity. As described in the previous embodiment, if LiMO2 with few impurities is synthesized, additives are added, and the material is heated again, the stability of the crystal structure after charging is improved. Therefore, for example, after LiMO2 is synthesized at a relatively high temperature of 800°C to 1200°C in the upstream portion, new materials such as magnesium, fluorine, nickel, and aluminum are added by the raw material supply means 113b, and then annealing is performed at a relatively low temperature of 700°C to 1000°C in the downstream portion, thereby producing a positive electrode active material with good characteristics.

[0255] <Vertical kiln> 12B, a vertical kiln 110c may be used. FIG. 12B is a schematic cross-sectional view of the kiln 110c. The kiln 110c has a kiln body 111b, heating means 112a and heating means 112b, a first mill 131a and a second mill 131b, and a raw material supply means 113.

[0256] The kiln body 111b is substantially cylindrical, and one end of the kiln body 111b is connected to the raw material supply means 113. The kiln body 111b has a scraper inside. The first mill 131a and the second mill 131b are provided inside the kiln body 111b. The upstream portion is the portion from the raw material supply means 113 to just before the first mill 131a. The downstream portion is the portion after the second mill 131b. In other words, the first mill 131a and the second mill 131b are provided between the upstream portion and the downstream portion.

[0257] The scraper or kiln body 111b has a function of stirring the material to be treated by rotating. It also has a function of retaining the material to be treated in the upstream portion for 1 hour or more and 100 hours or less. It also has a function of retaining the material to be treated in the downstream portion for 1 hour or more and 100 hours or less.

[0258] The first mill 131a and the second mill 131b function as a pair of millstones. The material to be processed is ground between the first mill 131a and the second mill 131b to prevent the material from sticking. At least one of the first mill 131a and the second mill 131b preferably has a groove on its surface.

[0259] The heating means 112a and the heating means 112b can be set to different heating temperatures. For example, the heating means 112a for heating the upstream portion preferably has a function of heating to 800° C. or more and 1200° C. or less. The heating means 112b for heating the downstream portion preferably has a function of heating to 700° C. or more and 1000° C. or less.

[0260] The raw material supply means 113 has a function of supplying the material to be treated to the upstream portion of the kiln main body 111b.

[0261] <Roller hearth kiln> The manufacturing apparatus according to one embodiment of the present invention may be a roller hearth kiln that continuously processes objects contained in a container. Fig. 13A is a cross-sectional schematic diagram of a roller hearth kiln 150. Fig. 13B is a diagram illustrating a plurality of rollers 152 of the roller hearth kiln.

[0262] The roller hearth kiln 150 has a kiln body 151, a plurality of rollers 152, heating means 153a and 153b, an atmosphere control means 154, and adhesion suppression means 155a, 155b and 155c. The roller hearth kiln 150 also preferably has blocking plates 157a, 157b and 157c, and measuring devices 120a and 120b.

[0263] The kiln body 151 is tunnel-shaped. A plurality of rollers 152 have the function of transporting a container 160 containing an object to be treated 161. The container 160 is transported by the plurality of rollers 152 through the tunnel-shaped kiln body 151 to the outside.

[0264] The kiln body 151 has an upstream portion and a downstream portion along the conveying direction of the multiple rollers 152. The kiln body 151 has a heating means 153a in the upstream portion and a heating means 153b in the downstream portion. A blocking plate 157b may be provided between the upstream portion and the downstream portion. By providing the blocking plate 157b, the atmosphere in the upstream portion and the downstream portion can be controlled separately. Also, the blocking plate 157b may be provided near the entrance of the kiln body 151, and the blocking plate 157c may be provided near the exit. By providing these, the atmosphere inside the kiln body 151 can be easily controlled.

[0265] The adhesion suppression means of the roller hearth kiln 150 is, for example, a means for vibrating the container 160. For example, the adhesion suppression means 155a, 155b, and 155c shown in FIG. 13A may be rod-shaped or plate-shaped devices provided between the multiple rollers 152. The adhesion suppression means 155a, 155b, and 155c may be fixed, or may move to vibrate the container 160. Although FIG. 13A shows a configuration in which three adhesion suppression means 155 are provided, one embodiment of the present invention is not limited to this. One or two adhesion suppression means 155 may be provided, or four or more adhesion suppression means may be provided.

[0266] The adhesion suppression means of the roller hearth kiln 150 may be a plurality of rollers 152 with different inclinations, as shown in FIG. 13B.

[0267] For the heating means 153a and 153b, the atmosphere control means 154, the measuring devices 120a and 120b, etc., the description of FIG. 11A can be referred to.

[0268] The roller hearth kiln 150 is preferable because it has high productivity since it continuously processes the materials to be treated.

[0269] The manufacturing apparatus according to one embodiment of the present invention may be a roller hearth kiln having a function of supplying new raw material during heating. Fig. 13C is a schematic cross-sectional view of a roller hearth kiln 150a having raw material supply means 158.

[0270] The roller hearth kiln 150a has a raw material supplying means 158 between the upstream and downstream parts of the kiln body 151. By having the raw material supplying means 158, it is possible to synthesize LiMO2 with few impurities, add additives by the raw material supplying means 158, and reheat, as in the case of the rotary kiln 110b shown in Fig. 12A. In this case, a container 160a without a lid is preferable as a container for holding the workpiece 161.

[0271] For other components, refer to the description of FIG. 13A.

[0272] <Mesh belt kiln> The manufacturing apparatus according to one embodiment of the present invention may be a mesh belt kiln that uses a mesh belt as a conveying means and continuously processes the objects to be processed contained in a container. FIG.

[0273] The mesh belt kiln 170 has a kiln body 171, a mesh belt 174, a heating means 173, and an adhesion suppression means 172. The mesh belt kiln 170 also preferably has a measuring device 120.

[0274] The kiln body 171 is tunnel-shaped. The mesh belt 174 has a function of transporting the container 160 containing the object to be treated 161. The container 160 passes through the tunnel-shaped kiln body 171 and is transported to the outside by the mesh belt 174.

[0275] The adhesion suppression means of the mesh belt kiln 170 is, for example, a means for vibrating the container 160. For example, as shown in FIG. 14A, the adhesion suppression means 172 may be an uneven device that vibrates the container 160 provided under the mesh belt 174. The adhesion suppression means 172 may be fixed, or may move to vibrate the container 160. Although FIG. 14A shows a configuration in which one adhesion suppression means 172 is provided, this is not a limitation of one embodiment of the present invention. A plurality of adhesion suppression means 172 may be provided. The length of the adhesion suppression means 172 may be approximately the same as the length of the kiln body 171.

[0276] The mesh belt kiln 170 is preferable because it has high productivity since it continuously processes the material to be treated. For other components, the description of FIG. 13A can be taken into consideration.

[0277] <Muffle furnace> The manufacturing apparatus according to one embodiment of the present invention may be a batch-type muffle furnace. FIG.

[0278] The muffle furnace 180 includes a hot plate 181, a heating means 182, a heat insulating material 183, an atmosphere control means 184, and an adhesion suppression means 185. The muffle furnace 180 preferably includes a measuring device 120.

[0279] The adhesion suppression means 185 of the muffle furnace 180 is a means for vibrating a container 190 containing a workpiece 191. The adhesion suppression means 185 shown in FIG.

[0280] The muffle furnace 180 is preferable because it is easy to control the atmosphere and temperature. For other components, the description of FIG. 13A can be referred to.

[0281] This embodiment mode can be used in appropriate combination with other embodiment modes.

[0282] (Embodiment 4) In this embodiment, an example of a secondary battery according to one aspect of the present invention will be described with reference to FIGS. 15 to 18.

[0283] <Example configuration 1 of a secondary battery> Hereinafter, a secondary battery in which a positive electrode, a negative electrode, and an electrolytic solution are wrapped in an exterior body will be described as an example.

[0284] 〔Positive electrode〕 The positive electrode has a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer has a positive electrode active material and may have a conductive material and a binder. As the positive electrode active material, the positive electrode active material produced by the production method described in the previous embodiment is used.

[0285] Also, the positive electrode active material described in the previous embodiment may be mixed with other positive electrode active materials and used.

[0286] Examples of other positive electrode active materials include composite oxides having an olivine-type crystal structure, a layered rock salt-type crystal structure, or a spinel-type crystal structure. For example, compounds such as LiFePO4, LiFeO2, LiNiO2, LiMn2O4, V2O5, Cr2O5, and MnO2 can be mentioned.

[0287] Also, as another positive electrode active material, a lithium-containing material having a spinel-type crystal structure containing manganese such as LiMn2O4 is mixed with lithium nickelate (LiNiO2 or LiNi 1-x M x O2 (0 <x <1) (M = Co, Al, etc.)) is preferably mixed. By adopting such a configuration, the characteristics of the secondary battery can be improved.

[0288] Also, as another positive electrode active material, a composition formula Li a Mn b M c O dIt is possible to use a lithium manganese composite oxide that can be expressed by the following formula. Here, the element M is preferably a metal element selected from lithium and manganese, or silicon or phosphorus, and more preferably nickel. When measuring the entire lithium manganese composite oxide particle, <a / (b+c)<2、かつc>it is preferable that the composition is 0 0 during discharge and 0.26≦(b+c) / d<0.5 is satisfied. The composition of metal, silicon, phosphorus, etc. of the entire lithium manganese composite oxide particle can be measured using, for example, an ICP-MS (inductively coupled plasma mass spectrometer). The composition of oxygen of the entire lithium manganese composite oxide particle can be measured using, for example, an EDX (energy dispersive X-ray spectrometry). It can also be obtained by using valence evaluation of melt gas analysis and XAFS (X-ray absorption fine structure) analysis in combination with ICPMS analysis. The lithium manganese composite oxide refers to an oxide containing at least lithium and manganese, and may contain at least one element selected from the group consisting of chromium, cobalt, aluminum, nickel, iron, magnesium, molybdenum, zinc, indium, gallium, copper, titanium, niobium, silicon, phosphorus, and the like.

[0289] As an example, a cross-sectional configuration example in the case where a graphene compound is used as a conductive material in the active material layer 200 will be described below.

[0290] 15A shows a vertical cross-sectional view of active material layer 200. Active material layer 200 includes granular positive electrode active material 100, graphene or a graphene compound 201 as a conductive material, and a binder (not shown).

[0291] ​In the present specification and the like, the graphene compound 201 includes multi-layer graphene, multi-graphene, graphene oxide, multi-layer graphene oxide, multi-graphene oxide, reduced graphene oxide, reduced multi-layer graphene oxide, reduced multi-graphene oxide, graphene quantum dots, and the like. The graphene compound has carbon, has a shape such as a plate shape or a sheet shape, and has a two-dimensional structure formed by six-membered carbon rings. The two-dimensional structure formed by six-membered carbon rings may be called a carbon sheet. The graphene compound may have a functional group. In addition, the graphene compound preferably has a bent shape. In addition, the graphene compound may be rolled up like a carbon nanofiber.

[0292] In this specification and the like, graphene oxide refers to a material that contains carbon and oxygen, has a sheet-like shape, and has a functional group, in particular, an epoxy group, a carboxy group, or a hydroxy group.

[0293] In the present specification and the like, reduced graphene oxide refers to a material having carbon and oxygen, a sheet-like shape, and a two-dimensional structure formed of six-membered carbon rings. It may be called a carbon sheet. Although reduced graphene oxide functions as a single sheet, multiple sheets may be stacked. Reduced graphene oxide preferably has a portion in which the carbon concentration is greater than 80 atomic % and the oxygen concentration is 2 atomic % or more and 15 atomic % or less. By setting such carbon concentration and oxygen concentration, it can function as a conductive material with high conductivity even in a small amount. In addition, reduced graphene oxide preferably has an intensity ratio G / D of G band to D band in Raman spectrum of 1 or more. Reduced graphene oxide with such intensity ratio can function as a conductive material with high conductivity even in a small amount.

[0294] In the vertical cross section of the active material layer 200, as shown in Fig. 15B, sheet-like graphene or graphene compound 201 is dispersed approximately uniformly inside the active material layer 200. In Fig. 15B, the graphene or graphene compound 201 is typically represented by a thick line, but is actually a thin film having a thickness of a single layer or multiple layers of carbon molecules. The multiple graphene or graphene compounds 201 are formed so as to partially cover the multiple granular positive electrode active materials 100 or to be attached to the surfaces of the multiple granular positive electrode active materials 100, and are therefore in surface contact with each other.

[0295] Here, a mesh-like graphene compound sheet (hereinafter referred to as a graphene compound net or graphene net) can be formed by bonding multiple graphenes or graphene compounds together. When an active material is covered with a graphene net, the graphene net can also function as a binder that bonds the active materials together. Therefore, the amount of binder can be reduced or no binder can be used, and the ratio of the active material to the electrode volume or weight can be improved. In other words, the capacity of the secondary battery can be increased.

[0296] Here, it is preferable to use graphene oxide as the graphene or graphene compound 201, mix it with an active material to form a layer that becomes the active material layer 200, and then reduce it. In other words, it is preferable that the completed active material layer has reduced graphene oxide. By using graphene oxide, which has extremely high dispersibility in a polar solvent, to form the graphene or graphene compound 201, it is possible to disperse the graphene or graphene compound 201 approximately uniformly inside the active material layer 200. Since the solvent is volatilized and removed from the dispersion medium containing the uniformly dispersed graphene oxide and the graphene oxide is reduced, the graphene or graphene compound 201 remaining in the active material layer 200 is dispersed to such an extent that it partially overlaps with each other and is in surface contact with each other, thereby forming a three-dimensional conductive path. The reduction of the graphene oxide may be performed, for example, by heat treatment or by using a reducing agent.

[0297] Therefore, unlike a granular conductive material such as acetylene black that makes point contact with the active material, graphene or the graphene compound 201 enables surface contact with low contact resistance, and therefore the electrical conductivity between the granular positive electrode active material 100 and the graphene or the graphene compound 201 can be improved with a smaller amount than that of a normal conductive material. Therefore, the ratio of the positive electrode active material 100 in the active material layer 200 can be increased. This can increase the discharge capacity of the secondary battery.

[0298] Furthermore, by using a spray drying apparatus in advance, a graphene compound, which is a conductive material, can be formed as a coating to cover the entire surface of the active material, and further a conductive path can be formed between adjacent particles of the active material by the graphene compound.

[0299] [Negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may include a conductive material and a binder.

[0300] [Negative electrode active material] As the negative electrode active material, for example, an alloy-based material or a carbon-based material can be used.

[0301] As the negative electrode active material, an element capable of carrying out a charge / discharge reaction by alloying / dealloying reaction with lithium can be used. For example, a material containing at least one of silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. can be used. Such elements have a larger capacity than carbon, and silicon in particular has a high theoretical capacity of 4200mAh / g. For this reason, it is preferable to use silicon as the negative electrode active material. Compounds containing these elements may also be used. For example, there are SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb, SbSn, etc. Here, elements capable of undergoing charge / discharge reactions through alloying / dealloying reactions with lithium, and compounds containing such elements, are sometimes referred to as alloying materials.

[0302] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO x Here, x preferably has a value close to 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.

[0303] Examples of the carbon-based material that can be used include graphite, easily graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon nanotubes, graphene, and carbon black.

[0304] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, MCMB may have a spherical shape, which is preferable. In addition, it is relatively easy to reduce the surface area of ​​MCMB, which may be preferable. Examples of natural graphite include flake graphite and spheroidized natural graphite.

[0305] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are formed), graphite exhibits a low potential similar to that of lithium metal (0.05 V to 0.3 V vs. Li / Li + ) This allows lithium-ion secondary batteries to exhibit high operating voltages. Furthermore, graphite is preferred because it has the advantages of relatively high capacity per unit volume, relatively small volume expansion, low cost, and high safety compared to lithium metal.

[0306] In addition, titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten oxide (WO2), molybdenum oxide (MoO2), and other oxides can be used.

[0307] In addition, the negative electrode active material is Li3N-type Li, a complex nitride of lithium and transition metals. 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 ) and is preferred.

[0308] When a composite nitride of lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, and therefore it is preferable to combine it with a material that does not contain lithium ions, such as V2O5 or Cr3O8, as the positive electrode active material. Even when a material that contains lithium ions is used as the positive electrode active material, the composite nitride of lithium and a transition metal can be used as the negative electrode active material by first removing the lithium ions contained in the positive electrode active material.

[0309] In addition, materials that undergo a conversion reaction can also be used as the negative electrode active material. For example, transition metal oxides that do not form an alloy with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as the negative electrode active material. Further examples of materials that undergo a conversion reaction include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, and CoS 0.89 It also occurs in sulfides such as NiS and CuS, nitrides such as Zn3N2, Cu3N and Ge3N4, phosphides such as NiP2, FeP2 and CoP3, and fluorides such as FeF3 and BiF3.

[0310] As the conductive material and binder that can be contained in the negative electrode active material layer, materials similar to the conductive material and binder that can be contained in the positive electrode active material layer can be used.

[0311] [Negative electrode current collector] The negative electrode current collector may be made of the same material as the positive electrode current collector, but it is preferable that the negative electrode current collector is made of a material that does not form an alloy with carrier ions such as lithium.

[0312] [Electrolyte] The electrolytic solution has a solvent and an electrolyte. The solvent of the electrolytic solution is preferably an aprotic organic solvent, and for example, one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc., or two or more of these can be used in any combination and ratio.

[0313] In addition, by using one or more ionic liquids (room-temperature molten salts) that are flame-retardant and non-volatile as a solvent for the electrolyte, even if the internal temperature of the secondary battery rises due to an internal short circuit or overcharging, the secondary battery can be prevented from bursting or catching fire. The ionic liquid is composed of a cation and an anion, and includes an organic cation and an anion. Examples of the organic cation used in the electrolyte include aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, and aromatic cations such as imidazolium cations and pyridinium cations. Examples of the anion used in the electrolyte include monovalent amide anions, monovalent methide anions, fluorosulfonic acid anions, perfluoroalkylsulfonic acid anions, tetrafluoroborate anions, perfluoroalkylborate anions, hexafluorophosphate anions, and perfluoroalkylphosphate anions.

[0314] Examples of the electrolyte to be dissolved in the above-mentioned solvent include LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, and Li2B 10 Cl 10 , Li2B 12 Cl 12 Lithium salts such as LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, etc. can be used alone or in any combination and ratio of two or more of these.

[0315] The electrolyte used in the secondary battery is preferably a highly purified electrolyte with a low content of granular dust and elements other than the constituent elements of the electrolyte (hereinafter, simply referred to as "impurities"). Specifically, the weight ratio of impurities to the electrolyte is preferably 1% or less, more preferably 0.1% or less, and even more preferably 0.01% or less.

[0316] In addition, additives such as vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate)borate (LiBOB), and dinitrile compounds such as succinonitrile and adiponitrile may be added to the electrolyte. The concentration of the additive may be, for example, 0.1 wt% to 5 wt% of the total solvent.

[0317] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution.

[0318] The use of a polymer gel electrolyte improves safety against leakage, etc. Also, it is possible to make the secondary battery thinner and lighter.

[0319] Examples of the polymer that can be gelled include silicone gel, acrylic gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, and fluorine-based polymer gel.

[0320] As the polymer, for example, a polymer having a polyalkylene oxide structure such as polyethylene oxide (PEO), PVDF, polyacrylonitrile, etc., and copolymers containing these can be used. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. The formed polymer may have a porous shape.

[0321] In addition, instead of the electrolyte, a solid electrolyte containing inorganic materials such as sulfides or oxides, or a solid electrolyte containing polymeric materials such as PEO (polyethylene oxide) can be used. When using a solid electrolyte, the installation of a separator or spacer becomes unnecessary. In addition, since the entire battery can be solidified, there is no risk of leakage, and safety is dramatically improved.

[0322] [Separator] The secondary battery preferably has a separator. The separator may be made of, for example, paper, nonwoven fabric, glass fiber, ceramics, or synthetic fibers such as nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester, acrylic, polyolefin, or polyurethane. The separator is preferably processed into an envelope shape and disposed so as to encase either the positive electrode or the negative electrode.

[0323] The separator may have a multi-layer structure. For example, an organic material film such as polypropylene or polyethylene may be coated with a ceramic material, a fluorine material, a polyamide material, or a mixture of these. As the ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As the fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As the polyamide material, for example, nylon or aramid (meta-aramid or para-aramid) may be used.

[0324] Coating with ceramic materials improves oxidation resistance, suppressing the deterioration of the separator during high-voltage charging and discharging, and improving the reliability of the secondary battery. Coating with fluorine-based materials also improves adhesion between the separator and electrodes, improving output characteristics. Coating with polyamide-based materials, especially aramid, improves heat resistance, improving the safety of the secondary battery.

[0325] For example, both sides of a polypropylene film may be coated with a mixture of aluminum oxide and aramid.Alternatively, the surface of the polypropylene film that contacts the positive electrode may be coated with a mixture of aluminum oxide and aramid, and the surface that contacts the negative electrode may be coated with a fluorine-based material.

[0326] By using a separator with a multi-layer structure, the safety of the secondary battery can be maintained even if the overall thickness of the separator is thin, and therefore the capacity per volume of the secondary battery can be increased.

[0327] [Exterior body] The exterior body of the secondary battery can be made of, for example, a metal material such as aluminum or a resin material. Also, a film-shaped exterior body can be used. As the film, for example, a three-layer structure film can be used in which a thin metal film having excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is provided on a film made of a material such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as a polyamide-based resin or polyester-based resin is further provided on the thin metal film as the outer surface of the exterior body.

[0328] <Secondary battery configuration example 2> As an example of the configuration of the secondary battery, the configuration of a secondary battery using a solid electrolyte layer will be described below.

[0329] As shown in FIG. 16A, a secondary battery 400 according to one embodiment of the present invention has a positive electrode 410, a solid electrolyte layer 420, and a negative electrode 430.

[0330] The positive electrode 410 includes a positive electrode current collector 413 and a positive electrode active material layer 414. The positive electrode active material layer 414 includes a positive electrode active material 411 and a solid electrolyte 421. The positive electrode active material 411 is formed using the positive electrode active material formed by the method described in the above embodiment. The positive electrode active material layer 414 may include a conductive additive and a binder.

[0331] Solid electrolyte layer 420 has solid electrolyte 421. Solid electrolyte layer 420 is located between positive electrode 410 and negative electrode 430, and is a region that has neither positive electrode active material 411 nor negative electrode active material 431.

[0332] The negative electrode 430 has a negative electrode current collector 433 and a negative electrode active material layer 434. The negative electrode active material layer 434 has a negative electrode active material 431 and a solid electrolyte 421. The negative electrode active material layer 434 may also have a conductive assistant and a binder. When metallic lithium is used for the negative electrode 430, the negative electrode 430 may not have a solid electrolyte 421, as shown in FIG. 16B. When metallic lithium is used for the negative electrode 430, the energy density of the secondary battery 400 can be improved, which is preferable.

[0333] As the solid electrolyte 421 of the solid electrolyte layer 420, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a halide-based solid electrolyte, or the like can be used.

[0334] Sulfide-based solid electrolytes include thiosilicon-based (Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, etc.), sulfide glass (70Li2S 30P2S5, 30Li2S 26B2S3 44LiI, 63Li2S 38SiS2 1Li3PO4, 57Li2S 38SiS2 5Li4SiO4, 50Li2S 50GeS2, etc.), sulfide crystallized glass (Li7P3S 11 , Li 3.25 P 0.95 Sulfide-based solid electrolytes have the advantages of being highly conductive, being able to be synthesized at low temperatures, and being relatively soft, making it easy to maintain conductive paths even after charging and discharging.

[0335] Oxide-based solid electrolytes include materials with a perovskite crystal structure (La 2 / 3-x Li 3x TiO3, etc.), materials with NASICON type crystal structure (Li 1-X Al X Ti 2-X (PO4)3, etc.), materials with garnet-type crystal structure (Li7La3Zr2O 12 etc.), materials with LISICON type crystal structure (Li 14 ZnGeO 16 etc.), LLZO(Li7La3Zr2O12 ), oxide glass (Li3PO4-Li4SiO4, 50Li4SiO4·50Li3BO3, etc.), oxide glass ceramics (Li 1.07 Al 0.69 Ti 1.46 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, etc. Oxide-based solid electrolytes have the advantage of being stable in the air.

[0336] Halide-based solid electrolytes include LiAlCl4, Li3InBr6, LiF, LiCl, LiBr, LiI, etc. Composite materials in which these halide-based solid electrolytes are filled into the pores of porous aluminum oxide or porous silica can also be used as solid electrolytes.

[0337] Also, different solid electrolytes may be used in combination.

[0338] Among them, Li with NASICON type crystal structure 1+x Al x Ti 2-x Since (PO4)3 (0≦x≦1) (hereinafter, LATP) contains aluminum and titanium, which are elements that may be contained in the positive electrode active material used in the secondary battery 400 of one embodiment of the present invention, a synergistic effect can be expected in improving cycle characteristics, which is preferable. In addition, an improvement in productivity can be expected by reducing the number of steps. In this specification and the like, the NASICON type crystal structure refers to a compound represented by M2(XO4)3 (M: transition metal, X: S, P, As, Mo, W, etc.), which has a structure in which MO6 octahedrons and XO4 tetrahedrons are arranged three-dimensionally with vertices shared.

[0339] [Shapes of exterior body and secondary battery] The exterior body of the secondary battery 400 of one embodiment of the present invention can be made of various materials and has various shapes, but preferably has a function of applying pressure to the positive electrode, the solid electrolyte layer, and the negative electrode.

[0340] For example, Figure 17 shows an example of a cell for evaluating materials for all-solid-state batteries.

[0341] 17A is a schematic cross-sectional view of the evaluation cell, which has a lower member 761, an upper member 762, and a fixing screw and a wing nut 764 that fix them, and the electrode plate 753 is pressed by rotating a holding screw 763 to fix the evaluation material. An insulator 766 is provided between the lower member 761 and the upper member 762, which are made of stainless steel. An O-ring 765 is provided between the upper member 762 and the holding screw 763 to seal.

[0342] The evaluation material is placed on electrode plate 751, surrounded by insulating tube 752, and pressed from above by electrode plate 753. An enlarged perspective view of the evaluation material and its periphery is shown in FIG. 17B.

[0343] The evaluation material is an example of a laminate of a positive electrode 750a, a solid electrolyte layer 750b, and a negative electrode 750c, and its cross-sectional view is shown in Fig. 17C. Note that the same reference numerals are used for the same parts in Fig. 17A, Fig. 17B, and Fig. 17C.

[0344] The electrode plate 751 and the lower member 761 electrically connected to the positive electrode 750a can be said to correspond to a positive electrode terminal. The electrode plate 753 and the upper member 762 electrically connected to the negative electrode 750c can be said to correspond to a negative electrode terminal. The electrical resistance and the like can be measured while applying pressure to the evaluation material via the electrode plate 751 and the electrode plate 753.

[0345] In addition, it is preferable to use a package with excellent airtightness for the exterior body of the secondary battery of one embodiment of the present invention. For example, a ceramic package or a resin package can be used. In addition, it is preferable to seal the exterior body in a sealed atmosphere, for example, in a glove box, while blocking the outside air.

[0346] Fig. 18A shows a perspective view of a secondary battery of one embodiment of the present invention, which has an exterior body and a shape different from those in Fig. 17. The secondary battery in Fig. 18A has external electrodes 771 and 772, and is sealed in an exterior body having a plurality of packaging members.

[0347] An example of a cross section cut along the dashed line in Fig. 18A is shown in Fig. 18B. A laminate having a positive electrode 750a, a solid electrolyte layer 750b, and a negative electrode 750c is surrounded and sealed by a package member 770a having an electrode layer 773a on a flat plate, a frame-shaped package member 770b, and a package member 770c having an electrode layer 773b on a flat plate. An insulating material such as a resin material or ceramic can be used for the package members 770a, 770b, and 770c.

[0348] The external electrode 771 is electrically connected to the positive electrode 750a via the electrode layer 773a and functions as a positive electrode terminal, while the external electrode 772 is electrically connected to the negative electrode 750c via the electrode layer 773b and functions as a negative electrode terminal.

[0349] This embodiment mode can be used in appropriate combination with other embodiment modes.

[0350] (Embodiment 5) In this embodiment, an example of the shape of a secondary battery having the positive electrode described in the previous embodiment will be described. The description in the previous embodiment can be referred to for the material used in the secondary battery described in this embodiment.

[0351] <Coin-type secondary battery> First, an example of a coin-type secondary battery will be described. Fig. 19A is an external view of a coin-type (single-layer flat) secondary battery, and Fig. 19B is a cross-sectional view thereof.

[0352] In the coin-type secondary battery 300, a positive electrode can 301, which also serves as a positive electrode terminal, and a negative electrode can 302, which also serves as a negative electrode terminal, are insulated and sealed with a gasket 303 made of polypropylene or the like. The positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector. The negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector.

[0353] In addition, the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 each need only have an active material layer formed on one side.

[0354] Metals such as nickel, aluminum, and titanium that are corrosion-resistant to the electrolyte, or alloys of these metals and other metals (e.g., stainless steel, etc.) can be used for the positive electrode can 301 and the negative electrode can 302. In order to prevent corrosion by the electrolyte, it is preferable to coat them with nickel, aluminum, etc. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.

[0355] These negative electrode 307, positive electrode 304, and separator 310 are impregnated with an electrolyte, and as shown in FIG. 19B, positive electrode can 301 is placed at the bottom, and positive electrode 304, separator 310, negative electrode 307, and negative electrode can 302 are stacked in this order, and positive electrode can 301 and negative electrode can 302 are crimped together via gasket 303, to produce coin-type secondary battery 300.

[0356] By using the positive electrode active material described in the above embodiment for the positive electrode 304, the coin-type secondary battery 300 can have a high capacity and excellent cycle characteristics.

[0357] Here, the flow of current during charging of a secondary battery will be described with reference to FIG. 19C. When a secondary battery using lithium is regarded as a closed circuit, the movement of lithium ions and the flow of current are in the same direction. In a secondary battery using lithium, the anode (positive electrode) and the cathode (negative electrode) are interchanged during charging and discharging, and the oxidation reaction and the reduction reaction are interchanged, so the electrode with a high reaction potential is called the positive electrode, and the electrode with a low reaction potential is called the negative electrode. Therefore, in this specification, the positive electrode is called the "positive electrode" or "+ electrode (plus electrode)" and the negative electrode is called the "negative electrode" or "- electrode (minus electrode)" whether during charging, discharging, when a reverse pulse current is applied, or when a charging current is applied. If the terms anode (positive electrode) and cathode (negative electrode) related to oxidation and reduction reactions are used, they may be reversed during charging and discharging, which may cause confusion. Therefore, the terms anode (positive electrode) and cathode (negative electrode) are not used in this specification. If the terms anode and cathode are used, it should be specified whether they are used during charging or discharging, and also whether they correspond to the positive electrode (plus) or negative electrode (minus).

[0358] 19C are connected to a charger to charge the secondary battery 300. As the charging of the secondary battery 300 progresses, the potential difference between the electrodes increases.

[0359] <Cylindrical secondary battery> Next, an example of a cylindrical secondary battery will be described with reference to Fig. 20. Fig. 20A shows an external view of a cylindrical secondary battery 600. Fig. 20B is a schematic diagram showing a cross section of the cylindrical secondary battery 600. As shown in Fig. 20B, the cylindrical secondary battery 600 has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (external can) 602 on the side and bottom surfaces. The positive electrode cap and the battery can (external can) 602 are insulated by a gasket (insulating packing) 610.

[0360] Inside a hollow cylindrical battery can 602, a battery element is provided in which a strip-shaped positive electrode 604 and a negative electrode 606 are wound with a separator 605 sandwiched therebetween. Although not shown, the battery element is wound around a center pin. One end of the battery can 602 is closed and the other end is open. For the battery can 602, metals such as nickel, aluminum, and titanium that are resistant to corrosion by the electrolyte, or alloys of these metals and other metals (e.g., stainless steel, etc.) can be used. In addition, in order to prevent corrosion by the electrolyte, it is preferable to coat the battery can 602 with nickel, aluminum, or the like. Inside the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched between a pair of opposing insulating plates 608 and 609. In addition, a nonaqueous electrolyte (not shown) is injected inside the battery can 602 in which the battery element is provided. The nonaqueous electrolyte can be the same as that of a coin-type secondary battery.

[0361] Since the positive and negative electrodes used in a cylindrical storage battery are wound, it is preferable to form an active material on both sides of the current collector. A positive electrode terminal (positive electrode current collector lead) 603 is connected to the positive electrode 604, and a negative electrode terminal (negative electrode current collector lead) 607 is connected to the negative electrode 606. Both the positive electrode terminal 603 and the negative electrode terminal 607 can be made of a metal material such as aluminum. The positive electrode terminal 603 is resistance-welded to a safety valve mechanism 612, and the negative electrode terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 612 is electrically connected to the positive electrode cap 601 via a PTC element (Positive Temperature Coefficient) 611. The safety valve mechanism 612 cuts off the electrical connection between the positive electrode cap 601 and the positive electrode 604 when the rise in the internal pressure of the battery exceeds a predetermined threshold value. The PTC element 611 is a thermosensitive resistor whose resistance increases when the temperature rises, and the increase in resistance limits the amount of current to prevent abnormal heat generation. Barium titanate (BaTiO3)-based semiconductor ceramics can be used for the PTC element.

[0362] 20C, a plurality of secondary batteries 600 may be sandwiched between conductive plates 613 and 614 to form a module 615. The plurality of secondary batteries 600 may be connected in parallel, in series, or in parallel and then further in series. By forming a module 615 having a plurality of secondary batteries 600, a large amount of power can be extracted.

[0363] FIG. 20D is a top view of the module 615. To clarify the drawing, the conductive plate 613 is shown by a dotted line. As shown in FIG. 20D, the module 615 may have a conductor 616 that electrically connects the multiple secondary batteries 600. A conductive plate can be provided by overlapping the conductor 616. Also, a temperature control device 617 may be provided between the multiple secondary batteries 600. When the secondary battery 600 is overheated, it can be cooled by the temperature control device 617, and when the secondary battery 600 is too cold, it can be heated by the temperature control device 617. Therefore, the performance of the module 615 is less susceptible to the influence of the outside air temperature. It is preferable that the heat medium of the temperature control device 617 is insulating and non-flammable.

[0364] By using the positive electrode active material described in the above embodiment for the positive electrode 604, the cylindrical secondary battery 600 can have a high capacity and excellent cycle characteristics.

[0365] <Structure example of secondary battery> Another structural example of the secondary battery will be described with reference to FIGS.

[0366] 21A and 21B are diagrams showing the external appearance of a battery pack. The battery pack has a secondary battery 913 and a circuit board 900. The secondary battery 913 is connected to an antenna 914 via the circuit board 900. A label 910 is attached to the secondary battery 913. As shown in FIG. 21B, the secondary battery 913 is connected to a terminal 951 and a terminal 952. The circuit board 900 is fixed with a sticker 915.

[0367] The circuit board 900 has a terminal 911 and a circuit 912. The terminal 911 is connected to a terminal 951, a terminal 952, an antenna 914, and the circuit 912. Note that a plurality of terminals 911 may be provided, and each of the plurality of terminals 911 may be a control signal input terminal, a power supply terminal, or the like.

[0368] The circuit 912 may be provided on the back surface of the circuit board 900. The antenna 914 is not limited to a coil shape, and may be, for example, a wire shape or a plate shape. In addition, an antenna such as a planar antenna, an aperture antenna, a traveling wave antenna, an EH antenna, a magnetic field antenna, or a dielectric antenna may be used. Alternatively, the antenna 914 may be a flat conductor. This flat conductor can function as one of the conductors for electric field coupling. In other words, the antenna 914 may function as one of the two conductors of the capacitor. This allows power to be exchanged not only by electromagnetic fields and magnetic fields, but also by electric fields.

[0369] The battery pack has a layer 916 between the antenna 914 and the secondary battery 913. The layer 916 has a function of, for example, shielding an electromagnetic field caused by the secondary battery 913. The layer 916 can be made of, for example, a magnetic material.

[0370] The structure of the battery pack is not limited to that shown in FIG.

[0371] For example, as shown in Fig. 22A and Fig. 22B, an antenna may be provided on each of a pair of opposing surfaces of the secondary battery 913 shown in Fig. 21A and Fig. 21B. Fig. 22A is an external view showing one of the pair of surfaces, and Fig. 22B is an external view showing the other of the pair of surfaces. Note that the description of the secondary battery shown in Fig. 21A and Fig. 21B can be used as appropriate for the same parts as those of the secondary battery shown in Fig. 21A and Fig. 21B.

[0372] 22A, an antenna 914 is provided on one of a pair of surfaces of a secondary battery 913 with a layer 916 sandwiched therebetween, and as shown in Fig. 22B, an antenna 918 is provided on the other of the pair of surfaces of the secondary battery 913 with a layer 917 sandwiched therebetween. The layer 917 has a function of, for example, being able to shield an electromagnetic field caused by the secondary battery 913. The layer 917 can be made of, for example, a magnetic material.

[0373] The above structure allows the sizes of both the antenna 914 and the antenna 918 to be increased. The antenna 918 has a function of performing data communication with, for example, an external device. For example, an antenna having a shape applicable to the antenna 914 can be applied to the antenna 918. As a communication method between the secondary battery and other devices via the antenna 918, a response method that can be used between the secondary battery and other devices, such as NFC (near field wireless communication), can be applied.

[0374] Alternatively, as shown in Fig. 22C, a display device 920 may be provided on the secondary battery 913 shown in Figs. 21A and 21B. The display device 920 is electrically connected to the terminal 911. Note that the label 910 does not need to be provided on the portion where the display device 920 is provided. Note that the description of the secondary battery shown in Figs. 21A and 21B can be appropriately applied to the same portions as those of the secondary battery shown in Figs. 21A and 21B.

[0375] For example, an image indicating whether charging is in progress, an image indicating the amount of stored power, etc. may be displayed on the display device 920. For example, electronic paper, a liquid crystal display device, an electroluminescence (EL) display device, etc. can be used as the display device 920. For example, the use of electronic paper can reduce the power consumption of the display device 920.

[0376] Alternatively, as shown in Fig. 22D, a sensor 921 may be provided in the secondary battery 913 shown in Fig. 21A and Fig. 21B. The sensor 921 is electrically connected to the terminal 911 via a terminal 922. Note that the description of the secondary battery shown in Fig. 21A and Fig. 21B can be appropriately applied to the same parts as those of the secondary battery shown in Fig. 21A and Fig. 21B.

[0377] The sensor 921 may have a function of measuring, for example, displacement, position, speed, acceleration, angular velocity, rotation speed, distance, light, liquid, magnetism, temperature, chemical substance, sound, time, hardness, electric field, current, voltage, power, radiation, flow rate, humidity, gradient, vibration, odor, or infrared ray. By providing the sensor 921, for example, data indicating the environment in which the secondary battery is placed (such as temperature) can be detected and stored in the memory in the circuit 912.

[0378] Further, a structural example of the secondary battery 913 will be described with reference to FIGS.

[0379] A secondary battery 913 shown in FIG. 23A has a wound body 950 in which terminals 951 and 952 are provided inside a housing 930. The wound body 950 is impregnated with an electrolyte inside the housing 930. The terminal 952 contacts the housing 930, and the terminal 951 does not contact the housing 930 by using an insulating material or the like. Note that in FIG. 23A, the housing 930 is shown separated for convenience, but in reality, the wound body 950 is covered by the housing 930, and the terminals 951 and 952 extend outside the housing 930. The housing 930 can be made of a metal material (e.g., aluminum) or a resin material.

[0380] As shown in Fig. 23B, the housing 930 shown in Fig. 23A may be formed from a plurality of materials. For example, the secondary battery 913 shown in Fig. 23B has a housing 930a and a housing 930b bonded together, and a wound body 950 is provided in the area surrounded by the housings 930a and 930b.

[0381] The housing 930a can be made of an insulating material such as organic resin. In particular, by using a material such as organic resin on the surface on which the antenna is formed, it is possible to suppress shielding of the electric field by the secondary battery 913. Note that if the shielding of the electric field by the housing 930a is small, an antenna such as the antenna 914 may be provided inside the housing 930a. The housing 930b can be made of, for example, a metal material.

[0382] 24 shows the structure of the wound body 950. The wound body 950 has a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is a wound body in which the negative electrode 931 and the positive electrode 932 are stacked on top of each other with the separator 933 in between, and the laminated sheet is wound. Note that the stack of the negative electrode 931, the positive electrode 932, and the separator 933 may be stacked a plurality of times.

[0383] 21 via one of the terminal 951 and the terminal 952. The positive electrode 932 is connected to the terminal 911 shown in FIG.

[0384] By using the positive electrode active material described in the above embodiment for the positive electrode 932, the secondary battery 913 can have high capacity and excellent cycle characteristics.

[0385] <Laminated secondary battery> Next, examples of laminated secondary batteries will be described with reference to Fig. 25 to Fig. 35. If the laminated secondary battery has a flexible configuration, and is mounted on an electronic device having at least a flexible portion, the secondary battery can be bent in accordance with the deformation of the electronic device.

[0386] A laminated secondary battery 980 will be described with reference to Fig. 25. The laminated secondary battery 980 has a wound body 993 shown in Fig. 25A. The wound body 993 has a negative electrode 994, a positive electrode 995, and a separator 996. The wound body 993 is formed by stacking the negative electrode 994 and the positive electrode 995 with the separator 996 sandwiched therebetween, in the same manner as the wound body 950 described in Fig. 24, and winding the laminated sheet.

[0387] The number of layers of the negative electrode 994, the positive electrode 995, and the separator 996 may be appropriately designed according to the required capacity and element volume. The negative electrode 994 is connected to a negative electrode current collector (not shown) via one of the lead electrodes 997 and 998, and the positive electrode 995 is connected to a positive electrode current collector (not shown) via the other of the lead electrodes 997 and 998.

[0388] As shown in Fig. 25B, a film 981 serving as an exterior body and a film 982 having a recess are bonded together by thermocompression or the like to form a space, and the above-mentioned wound body 993 is stored in the space, thereby producing a secondary battery 980 as shown in Fig. 25C. The wound body 993 has lead electrodes 997 and 998, and is impregnated with an electrolyte solution between the film 981 and the film 982 having a recess.

[0389] For example, a metal material such as aluminum or a resin material can be used for the film 981 and the film 982 having the recesses. If a resin material is used as the material for the film 981 and the film 982 having the recesses, the film 981 and the film 982 having the recesses can be deformed when an external force is applied, and a flexible storage battery can be produced.

[0390] Although an example in which two films are used is shown in FIG. 25B and FIG. 25C, a space may be formed by folding one film, and the above-mentioned wound body 993 may be housed in the space.

[0391] By using the positive electrode active material described in the above embodiment for the positive electrode 995, the secondary battery 980 can have a high capacity and excellent cycle characteristics.

[0392] In addition, in FIG. 25, an example of a secondary battery 980 having a wound body in a space formed by a film that serves as an outer casing is described. However, as shown in FIG. 26, for example, a secondary battery may also be used that has a plurality of rectangular positive electrodes, separators, and negative electrodes in a space formed by a film that serves as an outer casing.

[0393] 26A includes a positive electrode 503 having a positive electrode current collector 501 and a positive electrode active material layer 502, a negative electrode 506 having a negative electrode current collector 504 and a negative electrode active material layer 505, a separator 507, an electrolyte 508, and an exterior body 509. The separator 507 is disposed between the positive electrode 503 and the negative electrode 506 provided in the exterior body 509. The interior of the exterior body 509 is filled with the electrolyte 508. The electrolyte solution described in Embodiment 3 can be used as the electrolyte solution 508.

[0394] 26A, the positive electrode current collector 501 and the negative electrode current collector 504 also serve as terminals for obtaining electrical contact with the outside. Therefore, the positive electrode current collector 501 and the negative electrode current collector 504 may be arranged so as to be partially exposed to the outside from the exterior body 509. Alternatively, the positive electrode current collector 501 and the negative electrode current collector 504 may not be exposed to the outside from the exterior body 509, but may be exposed to the outside by using a lead electrode and ultrasonically bonding the lead electrode to the positive electrode current collector 501 or the negative electrode current collector 504.

[0395] In the laminated secondary battery 500, the exterior body 509 may be a three-layer laminate film having a highly flexible thin metal film such as aluminum, stainless steel, copper, nickel, etc., provided on a film made of a material such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and further having an insulating synthetic resin film such as a polyamide-based resin, polyester-based resin, etc., provided on the thin metal film as the outer surface of the exterior body.

[0396] 26B shows an example of a cross-sectional structure of a laminated secondary battery 500. For simplicity, Fig. 26A shows an example of a battery made up of two current collectors, but in reality, the battery is made up of multiple electrode layers as shown in Fig. 26B.

[0397] In FIG. 26B, the number of electrode layers is 16 as an example. Even if the number of electrode layers is 16, the secondary battery 500 has flexibility. FIG. 26B shows a structure of 16 layers in total, including 8 layers of negative electrode collector 504 and 8 layers of positive electrode collector 501. FIG. 26B shows a cross section of the negative electrode lead-out portion, in which 8 layers of negative electrode collector 504 are ultrasonically bonded. Of course, the number of electrode layers is not limited to 16, and may be more or less. When the number of electrode layers is large, a secondary battery having a larger capacity can be obtained. Also, when the number of electrode layers is small, a secondary battery that can be made thin and has excellent flexibility can be obtained.

[0398] 27 and 28 show an example of an external view of a laminated secondary battery 500. In Fig. 27 and Fig. 28, a positive electrode 503, a negative electrode 506, a separator 507, an exterior body 509, a positive electrode lead electrode 510, and a negative electrode lead electrode 511 are provided.

[0399] FIG. 29A shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 has a positive electrode current collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. The positive electrode 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). The negative electrode 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. The negative electrode 506 has a region where the negative electrode current collector 504 is partially exposed, that is, a tab region. The areas and shapes of the tab regions of the positive electrode and the negative electrode are not limited to the example shown in FIG. 29A.

[0400] <Method of manufacturing laminated secondary battery> Here, an example of a method for producing the laminate type secondary battery whose external view is shown in FIG. 27 will be described with reference to FIGS. 29B and 29C.

[0401] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. FIG. 29B shows the laminated negative electrode 506, the separator 507, and the positive electrode 503. Here, an example is shown in which five pairs of negative electrodes and four pairs of positive electrodes are used. Next, the tab regions of the positive electrodes 503 are joined together, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. For example, ultrasonic welding or the like may be used for the joining. Similarly, the tab regions of the negative electrodes 506 are joined together, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.

[0402] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .

[0403] Next, as shown in Fig. 29C, exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of exterior body 509 is joined. For the joining, for example, thermocompression bonding or the like may be used. At this time, a region (hereinafter referred to as an inlet) that is not joined is provided in a part (or one side) of exterior body 509 so that electrolyte 508 can be poured in later.

[0404] Next, electrolytic solution 508 (not shown) is introduced into the inside of exterior body 509 through an inlet provided in exterior body 509. The introduction of electrolytic solution 508 is preferably performed under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is joined. In this manner, laminated secondary battery 500 can be produced.

[0405] By using the positive electrode active material described in the above embodiment for the positive electrode 503, the secondary battery 500 can have a high capacity and excellent cycle characteristics.

[0406] In an all-solid-state battery, the contact state of the internal interfaces can be maintained good by applying a predetermined pressure in the stacking direction of the stacked positive and negative electrodes. By applying a predetermined pressure in the stacking direction of the positive and negative electrodes, expansion in the stacking direction due to charging and discharging of the all-solid-state battery can be suppressed, and the reliability of the all-solid-state battery can be improved.

[0407] This embodiment mode can be used in appropriate combination with other embodiment modes.

[0408] (Embodiment 6) In this embodiment, an example in which a secondary battery which is one embodiment of the present invention is mounted on an electronic device will be described.

[0409] First, examples of electronic devices incorporating the bendable secondary battery described in the previous embodiment are shown in Figures 30A to 30G. Examples of electronic devices to which the bendable secondary battery is applied include television devices (also called televisions or television receivers), computer monitors, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game machines, personal digital assistants, audio playback devices, and large game machines such as pachinko machines.

[0410] Furthermore, a secondary battery having a flexible shape can be incorporated into the inner or outer wall of a house or building, or along the curved surface of the interior or exterior of an automobile.

[0411] 30A illustrates an example of a mobile phone. A mobile phone 7400 includes a display portion 7402 built into a housing 7401, operation buttons 7403, an external connection port 7404, a speaker 7405, a microphone 7406, and the like. Note that the mobile phone 7400 includes a secondary battery 7407. By using the secondary battery of one embodiment of the present invention as the secondary battery 7407, a lightweight mobile phone with a long life can be provided.

[0412] FIG. 30B shows a state in which the mobile phone 7400 is bent. When the mobile phone 7400 is deformed by an external force and bent as a whole, the secondary battery 7407 provided therein is also bent. FIG. 30C shows the state of the bent secondary battery 7407 at that time. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is fixed in a bent state. The secondary battery 7407 has a lead electrode electrically connected to the current collector. For example, the current collector is a copper foil, and a part of the copper foil is alloyed with gallium to improve adhesion with the active material layer in contact with the current collector, so that the secondary battery 7407 has a high reliability when bent.

[0413] FIG. 30D illustrates an example of a bangle-type display device. The portable display device 7100 includes a housing 7101, a display unit 7102, an operation button 7103, and a secondary battery 7104. FIG. 30E illustrates a bent state of the secondary battery 7104. When the secondary battery 7104 is worn on a user's arm in a bent state, the housing is deformed, and the curvature of the secondary battery 7104 changes in part or in whole. Note that the degree of bending at any point of the curve expressed by the value of the radius of the corresponding circle is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. Specifically, the housing or the main surface of the secondary battery 7104 changes in part or in whole when the radius of curvature is in the range of 40 mm to 150 mm. High reliability can be maintained if the radius of curvature of the main surface of the secondary battery 7104 is in the range of 40 mm to 150 mm. By using the secondary battery of one embodiment of the present invention as the secondary battery 7104, a lightweight portable display device with a long life can be provided.

[0414] 30F shows an example of a wristwatch-type portable information terminal 7200. A portable information terminal 7200 includes a housing 7201, a display portion 7202, a band 7203, a buckle 7204, operation buttons 7205, an input / output terminal 7206, and the like.

[0415] The portable information terminal 7200 can execute various applications such as mobile telephone, e-mail, document browsing and creation, music playback, Internet communication, and computer games.

[0416] The display surface of the display portion 7202 is curved, and display can be performed along the curved display surface. The display portion 7202 is also provided with a touch sensor, and can be operated by touching the screen with a finger, a stylus, or the like. For example, an application can be started by touching an icon 7207 displayed on the display portion 7202.

[0417] The operation button 7205 can have various functions, such as time setting, power on / off operation, wireless communication on / off operation, silent mode activation / cancellation, power saving mode activation / cancellation, etc. For example, the function of the operation button 7205 can be freely set by an operating system built into the mobile information terminal 7200.

[0418] The mobile information terminal 7200 can also perform short-distance wireless communication according to a communication standard. For example, the mobile information terminal 7200 can communicate with a wireless headset to enable hands-free calling.

[0419] The portable information terminal 7200 also includes an input / output terminal 7206, and can directly exchange data with another information terminal via a connector. Charging can also be performed via the input / output terminal 7206. Note that charging may be performed by wireless power supply without using the input / output terminal 7206.

[0420] The display portion 7202 of the portable information terminal 7200 includes the secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a lightweight portable information terminal with a long life can be provided. For example, the secondary battery 7104 shown in FIG. 30E can be incorporated in a curved state inside the housing 7201 or in a bendable state inside the band 7203.

[0421] The portable information terminal 7200 preferably has a sensor. For example, it is preferable to mount a human body sensor such as a fingerprint sensor, a pulse sensor, or a body temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, or the like, as the sensor.

[0422] 30G illustrates an example of an armband-type display device. The display device 7300 includes a display portion 7304 and a secondary battery of one embodiment of the present invention. The display device 7300 can also include a touch sensor in the display portion 7304 and can function as a portable information terminal.

[0423] The display surface of the display portion 7304 is curved, and display can be performed along the curved display surface. In addition, the display device 7300 can change the display state by short-range wireless communication according to a communication standard.

[0424] The display device 7300 also includes an input / output terminal, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the input / output terminal. Note that charging may be performed by wireless power supply without using the input / output terminal.

[0425] By using the secondary battery of one embodiment of the present invention as a secondary battery included in the display device 7300, a lightweight display device with a long lifetime can be provided.

[0426] Moreover, an example in which the secondary battery having good cycle characteristics shown in the above embodiment is mounted in an electronic device will be described with reference to FIGS. 30H, 31, and 32. FIG.

[0427] By using the secondary battery of one embodiment of the present invention as a secondary battery in daily electronic devices, products that are lightweight and have a long life can be provided. For example, daily electronic devices include electric toothbrushes, electric shavers, and electric beauty devices. For the secondary battery of these products, a stick-shaped, small, lightweight, and large-capacity secondary battery is desired in consideration of ease of holding by users.

[0428] FIG. 30H is a perspective view of a device also called a tobacco-receiving smoking device (electronic cigarette). In FIG. 30H, the electronic cigarette 7500 is composed of an atomizer 7501 including a heating element, a secondary battery 7504 that supplies power to the atomizer, and a cartridge 7502 including a liquid supply bottle, a sensor, and the like. To enhance safety, a protection circuit that prevents overcharging and overdischarging of the secondary battery 7504 may be electrically connected to the secondary battery 7504. The secondary battery 7504 shown in FIG. 30H has an external terminal so that it can be connected to a charging device. Since the secondary battery 7504 is the tip part when held, it is desirable that the total length is short and the weight is light. Since the secondary battery of one embodiment of the present invention has a high capacity and good cycle characteristics, a small and lightweight electronic cigarette 7500 that can be used for a long period of time can be provided.

[0429] Next, an example of a tablet terminal that can be folded in two is shown in Fig. 31A and Fig. 31B. The tablet terminal 9600 shown in Fig. 31A and Fig. 31B has a housing 9630a, a housing 9630b, a movable part 9640 that connects the housings 9630a and 9630b, a display part 9631 having a display part 9631a and a display part 9631b, switches 9625 to 9627, a fastener 9629, and an operation switch 9628. By using a flexible panel for the display part 9631, a tablet terminal having a wider display part can be obtained. Fig. 31A shows the tablet terminal 9600 in an open state, and Fig. 31B shows the tablet terminal 9600 in a closed state.

[0430] The tablet terminal 9600 also includes a power storage unit 9635 inside the housing 9630a and the housing 9630b. The power storage unit 9635 passes through the movable portion 9640 and is provided across the housings 9630a and 9630b.

[0431] The entire or part of the display portion 9631 can be a touch panel area, and data can be input by touching an image including an icon, text, an input form, etc. displayed in the area. For example, keyboard buttons may be displayed on the entire surface of the display portion 9631a on the housing 9630a side, and information such as text and images may be displayed on the display portion 9631b on the housing 9630b side.

[0432] A keyboard may be displayed on the display portion 9631b of the housing 9630b, and information such as text and images may be displayed on the display portion 9631a of the housing 9630a. A keyboard display switching button of a touch panel may be displayed on the display portion 9631, and a keyboard may be displayed on the display portion 9631 by touching the button with a finger, a stylus, or the like.

[0433] In addition, a touch input can be simultaneously made to the touch panel area of ​​the display portion 9631a on the housing 9630a side and the touch panel area of ​​the display portion 9631b on the housing 9630b side.

[0434] The switches 9625 to 9627 may be interfaces capable of switching various functions in addition to interfaces for operating the tablet terminal 9600. For example, at least one of the switches 9625 to 9627 may function as a switch for switching on and off the power of the tablet terminal 9600. For example, at least one of the switches 9625 to 9627 may have a function for switching the display orientation, such as portrait or landscape, or a function for switching between black and white or color display. For example, at least one of the switches 9625 to 9627 may have a function for adjusting the brightness of the display unit 9631. The brightness of the display unit 9631 can be optimized according to the amount of external light during use detected by an optical sensor built into the tablet terminal 9600. Note that the tablet terminal may have built-in not only an optical sensor but also other detection devices such as a gyro, an acceleration sensor, or the like for detecting tilt.

[0435] 31A shows an example in which the display area of ​​the display portion 9631a on the housing 9630a side and the display portion 9631b on the housing 9630b side are substantially the same, but the display areas of the display portions 9631a and 9631b are not particularly limited, and one may have a different size from the other, and the display quality may also be different. For example, one may be a display panel that can display with higher resolution than the other.

[0436] 31B shows a tablet terminal 9600 folded in half, and the tablet terminal 9600 includes a housing 9630, a solar cell 9633, and a charge / discharge control circuit 9634 including a DC-DC converter 9636. In addition, a power storage unit according to one embodiment of the present invention is used as a power storage unit 9635.

[0437] As described above, the tablet terminal 9600 can be folded in two, and therefore the housing 9630a and the housing 9630b can be folded so as to overlap each other when not in use. By folding, the display portion 9631 can be protected, and therefore durability of the tablet terminal 9600 can be improved. Furthermore, the power storage unit 9635 using the secondary battery of one embodiment of the present invention has a high capacity and favorable cycle characteristics, and therefore the tablet terminal 9600 that can be used for a long period of time can be provided.

[0438] In addition, the tablet terminal 9600 shown in Figures 31A and 31B can have a function to display various information (still images, videos, text images, etc.), a function to display a calendar, date or time on the display unit, a touch input function to perform touch input operations or edit information displayed on the display unit, and a function to control processing using various software (programs), etc.

[0439] A solar cell 9633 attached to the surface of the tablet terminal 9600 can supply power to a touch panel, a display unit, a video signal processor, or the like. The solar cell 9633 can be provided on one or both sides of the housing 9630, and can be configured to efficiently charge the power storage unit 9635. The use of a lithium ion battery as the power storage unit 9635 has the advantage of enabling miniaturization.

[0440] The configuration and operation of the charge / discharge control circuit 9634 shown in Fig. 31B are described with reference to a block diagram in Fig. 31C. Fig. 31C shows a solar cell 9633, a power storage unit 9635, a DCDC converter 9636, a converter 9637, switches SW1 to SW3, and a display unit 9631. The power storage unit 9635, the DCDC converter 9636, the converter 9637, and the switches SW1 to SW3 correspond to the charge / discharge control circuit 9634 shown in Fig. 31B.

[0441] First, an example of operation in the case where power is generated by the solar cell 9633 using external light will be described. The power generated by the solar cell is stepped up or stepped down by a DC-DC converter 9636 to a voltage for charging a power storage unit 9635. When power from the solar cell 9633 is used for the operation of the display unit 9631, a switch SW1 is turned on, and the converter 9637 steps up or steps down the voltage to a voltage required for the display unit 9631. When no display is to be performed on the display unit 9631, SW1 is turned off and SW2 is turned on to charge the power storage unit 9635.

[0442] Note that the solar cell 9633 is shown as an example of a power generating means, but is not particularly limited thereto, and may be configured to charge the power storage unit 9635 using other power generating means such as a piezoelectric element (piezo element) or a thermoelectric conversion element (Peltier element). For example, a non-contact power transmission module that transmits and receives power wirelessly (non-contact) for charging, or a combination with other charging means may be used.

[0443] FIG. 32 illustrates an example of another electronic device. In FIG. 32, a display device 8000 is an example of an electronic device using a secondary battery 8004 according to one embodiment of the present invention. Specifically, the display device 8000 corresponds to a display device for receiving a TV broadcast and includes a housing 8001, a display unit 8002, a speaker unit 8003, a secondary battery 8004, and the like. The secondary battery 8004 according to one embodiment of the present invention is provided inside the housing 8001. The display device 8000 can receive power from a commercial power source, and can also use power stored in the secondary battery 8004. Thus, even when power cannot be supplied from a commercial power source due to a power outage or the like, the display device 8000 can be used by using the secondary battery 8004 according to one embodiment of the present invention as an uninterruptible power source.

[0444] The display unit 8002 can be a liquid crystal display device, a light-emitting device having a light-emitting element such as an organic EL element in each pixel, an electrophoretic display device, a semiconductor display device such as a DMD (Digital Micromirror Device), a PDP (Plasma Display Panel), or an FED (Field Emission Display).

[0445] The display device includes all display devices for displaying information, such as display devices for receiving TV broadcasts, display devices for personal computers, display devices for advertisements, and the like.

[0446] In FIG. 32, a stationary lighting device 8100 is an example of an electronic device using a secondary battery 8103 according to one embodiment of the present invention. Specifically, the lighting device 8100 includes a housing 8101, a light source 8102, a secondary battery 8103, and the like. FIG. 32 illustrates an example in which the secondary battery 8103 is provided inside a ceiling 8104 on which the housing 8101 and the light source 8102 are provided, but the secondary battery 8103 may be provided inside the housing 8101. The lighting device 8100 can receive power from a commercial power source or can use power stored in the secondary battery 8103. Thus, even when power cannot be supplied from a commercial power source due to a power outage or the like, the lighting device 8100 can be used by using the secondary battery 8103 according to one embodiment of the present invention as an uninterruptible power source.

[0447] Note that although Figure 32 shows an example of a stationary lighting device 8100 provided on a ceiling 8104, the secondary battery of one embodiment of the present invention can also be used in a stationary lighting device provided on a surface other than the ceiling 8104, such as a side wall 8105, a floor 8106, or a window 8107, or can also be used in a tabletop lighting device.

[0448] An artificial light source that artificially obtains light using electric power can be used as the light source 8102. Specifically, examples of the artificial light source include discharge lamps such as incandescent lamps and fluorescent lamps, and light-emitting elements such as LEDs and organic EL elements.

[0449] In FIG. 32, an air conditioner including an indoor unit 8200 and an outdoor unit 8204 is an example of an electronic device using a secondary battery 8203 according to one embodiment of the present invention. Specifically, the indoor unit 8200 includes a housing 8201, an air outlet 8202, a secondary battery 8203, and the like. FIG. 32 illustrates an example in which the secondary battery 8203 is provided in the indoor unit 8200, but the secondary battery 8203 may be provided in the outdoor unit 8204. Alternatively, the secondary battery 8203 may be provided in both the indoor unit 8200 and the outdoor unit 8204. The air conditioner can receive power from a commercial power source or can use power stored in the secondary battery 8203. In particular, when a secondary battery 8203 is provided in both the indoor unit 8200 and the outdoor unit 8204, even when power cannot be supplied from a commercial power source due to a power outage or the like, the air conditioner can be used by using the secondary battery 8203 of one embodiment of the present invention as an uninterruptible power source.

[0450] Note that although FIG. 32 illustrates an example of a separate-type air conditioner including an indoor unit and an outdoor unit, a secondary battery according to one embodiment of the present invention can also be used in an integrated air conditioner that has the functions of an indoor unit and an outdoor unit in a single housing.

[0451] 32, an electric refrigerator-freezer 8300 is an example of an electronic device using a secondary battery 8304 according to one embodiment of the present invention. Specifically, the electric refrigerator-freezer 8300 includes a housing 8301, a refrigerator door 8302, a freezer door 8303, a secondary battery 8304, and the like. In FIG. 32, the secondary battery 8304 is provided inside the housing 8301. The electric refrigerator-freezer 8300 can receive power from a commercial power source or can use power stored in the secondary battery 8304. Thus, even when power cannot be supplied from the commercial power source due to a power outage or the like, the electric refrigerator-freezer 8300 can be used by using the secondary battery 8304 according to one embodiment of the present invention as an uninterruptible power source.

[0452] Among the electronic devices described above, electronic devices such as high-frequency heating devices such as microwave ovens and electric rice cookers require a large amount of power for a short period of time. Therefore, by using a secondary battery according to one embodiment of the present invention as an auxiliary power source for supplementing the power that cannot be supplied by the commercial power source, it is possible to prevent the breaker of the commercial power source from tripping when the electronic device is in use.

[0453] Also, by storing power in the secondary battery during time periods when electronic devices are not used, particularly during time periods when the ratio of the amount of power actually used to the total amount of power that can be supplied by the commercial power source (called the power usage rate) is low, it is possible to prevent the power usage rate from increasing outside of the above time periods. For example, in the case of an electric refrigerator-freezer 8300, power is stored in the secondary battery 8304 during the night when the temperature is low and the refrigerator door 8302 and the freezer door 8303 are not opened or closed. Then, during the daytime when the temperature is high and the refrigerator door 8302 and the freezer door 8303 are opened and closed, the secondary battery 8304 is used as an auxiliary power source, thereby making it possible to keep the daytime power usage rate low.

[0454] According to one embodiment of the present invention, the cycle characteristics of the secondary battery are improved, and the reliability can be improved. According to one embodiment of the present invention, a high-capacity secondary battery can be obtained, and therefore the characteristics of the secondary battery can be improved, and therefore the secondary battery itself can be made smaller and lighter. Therefore, by mounting the secondary battery according to one embodiment of the present invention in the electronic device described in this embodiment, the electronic device can have a longer life and be lighter.

[0455] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0456] (Embodiment 7) In this embodiment, examples of electronic devices using the secondary battery described in the above embodiment will be described with reference to FIGS.

[0457] Fig. 33A shows an example of a wearable device. The wearable device uses a secondary battery as a power source. In addition, when a user uses the device in daily life or outdoors, in order to improve splash-proof performance, water resistance, or dust-proof performance, a wearable device that can be charged wirelessly as well as by wire with an exposed connector is desired.

[0458] For example, the secondary battery according to one embodiment of the present invention can be mounted on a glasses-type device 4000 as shown in FIG. 33A. The glasses-type device 4000 has a frame 4000a and a display unit 4000b. By mounting a secondary battery on the temples of the curved frame 4000a, the glasses-type device 4000 can be made lightweight, well-balanced in weight, and capable of long continuous use. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a smaller housing can be realized.

[0459] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the headset type device 4001. The headset type device 4001 has at least a microphone unit 4001a, a flexible pipe 4001b, and an earphone unit 4001c. The secondary battery can be provided in the flexible pipe 4001b or the earphone unit 4001c. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a miniaturized housing can be realized.

[0460] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4002 that can be directly attached to the body. A secondary battery 4002b can be provided in a thin housing 4002a of the device 4002. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0461] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4003 that can be attached to clothing. A secondary battery 4003b can be provided in a thin housing 4003a of the device 4003. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0462] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the belt type device 4006. The belt type device 4006 has a belt portion 4006a and a wireless power receiving portion 4006b, and a secondary battery can be mounted inside the belt portion 4006a. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with miniaturization of the housing can be realized.

[0463] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the wristwatch device 4005. The wristwatch device 4005 has a display portion 4005a and a belt portion 4005b, and the secondary battery can be provided on the display portion 4005a or the belt portion 4005b. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0464] The display unit 4005a can display not only the time, but also various other information such as incoming e-mails and phone calls.

[0465] In addition, since the wristwatch type device 4005 is a wearable device that is directly wrapped around the arm, it may be equipped with sensors that measure the user's pulse, blood pressure, etc. Data on the user's amount of exercise and health can be accumulated to manage the user's health.

[0466] FIG. 33B shows a perspective view of the wristwatch type device 4005 removed from the wrist.

[0467] 33C shows a side view of the display portion 4005. FIG. 33C shows a state in which a secondary battery 913 is built in the display portion 4005. The secondary battery 913 is the secondary battery described in Embodiment 5. The secondary battery 913 is provided at a position overlapping with the display portion 4005a, and is small and lightweight.

[0468] 34A shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 arranged on the top surface of a housing 6301, a plurality of cameras 6303 arranged on the side surface, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, and the like. Although not shown, the cleaning robot 6300 is provided with tires, a suction port, and the like. The cleaning robot 6300 can move by itself, detect dust 6310, and suck up the dust from a suction port provided on the bottom surface.

[0469] For example, the cleaning robot 6300 can analyze an image captured by the camera 6303 and determine the presence or absence of an obstacle such as a wall, furniture, or a step. When an object that may become entangled in the brush 6304, such as a wire, is detected by image analysis, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 includes a secondary battery 6306 according to one embodiment of the present invention and a semiconductor device or electronic component therein. By using the secondary battery 6306 according to one embodiment of the present invention in the cleaning robot 6300, the cleaning robot 6300 can be an electronic device with long operating time and high reliability.

[0470] Fig. 34B shows an example of a robot. The robot 6400 shown in Fig. 34B includes a secondary battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0471] The microphone 6402 has a function of detecting the user's voice, environmental sounds, etc. The speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user using the microphone 6402 and the speaker 6404.

[0472] The display unit 6405 has a function of displaying various information. The robot 6400 can display information desired by the user on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may also be a removable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer are possible.

[0473] The upper camera 6403 and the lower camera 6406 have a function of capturing images of the surroundings of the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of an obstacle in the moving direction when the robot 6400 moves forward using the moving mechanism 6408. The robot 6400 can recognize the surrounding environment and move safely using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407.

[0474] The robot 6400 includes a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or electronic component inside the robot 6400. By using the secondary battery according to one embodiment of the present invention in the robot 6400, the robot 6400 can be a highly reliable electronic device with a long operating time.

[0475] Fig. 34C shows an example of an aircraft. An aircraft 6500 shown in Fig. 34C has a propeller 6501, a camera 6502, a secondary battery 6503, and the like, and has a function of flying autonomously.

[0476] For example, image data captured by the camera 6502 is stored in the electronic component 6504. The electronic component 6504 can analyze the image data and detect the presence or absence of an obstacle when moving. The electronic component 6504 can estimate the remaining battery charge from a change in the power storage capacity of the secondary battery 6503. The flying object 6500 includes therein the secondary battery 6503 according to one embodiment of the present invention. By using the secondary battery according to one embodiment of the present invention in the flying object 6500, the flying object 6500 can be an electronic device with a long operating time and high reliability.

[0477] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0478] (Embodiment 8) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on a vehicle will be described.

[0479] By installing a secondary battery in a vehicle, next-generation clean energy vehicles such as hybrid electric vehicles (HEV), electric vehicles (EV), and plug-in hybrid electric vehicles (PHEV) can be realized.

[0480] FIG. 35 illustrates a vehicle using a secondary battery according to one embodiment of the present invention. An automobile 8400 illustrated in FIG. 35A is an electric automobile using an electric motor as a power source for running. Alternatively, it is a hybrid automobile that can appropriately select and use an electric motor and an engine as a power source for running. By using one embodiment of the present invention, a vehicle with a long cruising distance can be realized. The automobile 8400 also includes a secondary battery. The secondary battery may be used by arranging modules of the secondary battery illustrated in FIG. 20C and FIG. 20D on the floor of the vehicle. Alternatively, a battery pack in which a plurality of secondary batteries illustrated in FIG. 23 are combined may be installed on the floor of the vehicle. The secondary battery not only drives the electric motor 8406 but also supplies power to a light-emitting device such as a headlight 8401 or a room light (not shown).

[0481] The secondary battery can also supply power to display devices such as a speedometer and a tachometer included in the automobile 8400. The secondary battery can also supply power to semiconductor devices such as a navigation system included in the automobile 8400.

[0482] The automobile 8500 shown in FIG. 35B can charge the secondary battery of the automobile 8500 by receiving power supply from an external charging facility by a plug-in method, a non-contact power supply method, or the like. FIG. 35B shows a state in which a secondary battery 8024 mounted on the automobile 8500 is being charged from a ground-mounted charging device 8021 via a cable 8022. When charging, the charging method and connector standards may be appropriately performed by a predetermined method such as CHAdeMO (registered trademark) or Combo. The charging device 8021 may be a charging station installed in a commercial facility, or may be a home power source. For example, the secondary battery 8024 mounted on the automobile 8500 can be charged by an external power supply using plug-in technology. Charging can be performed by converting AC power to DC power via a conversion device such as an ACDC converter.

[0483] Although not shown, a power receiving device may be mounted on a vehicle, and charging may be performed by supplying power contactlessly from a ground power transmitting device. In the case of this contactless power supply method, by incorporating a power transmitting device in a road or an exterior wall, charging may be performed not only while the vehicle is stopped but also while the vehicle is moving. This contactless power supply method may also be used to transmit and receive power between vehicles. Furthermore, a solar cell may be provided on the exterior of the vehicle, and a secondary battery may be charged while the vehicle is stopped or moving. For such contactless power supply, an electromagnetic induction method or a magnetic field resonance method may be used.

[0484] 35C is an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. A scooter 8600 shown in FIG 35C includes a secondary battery 8602, a side mirror 8601, and a turn signal light 8603. The secondary battery 8602 can supply electricity to the turn signal light 8603.

[0485] 35C, the secondary battery 8602 can be stored in the under-seat storage 8604. Even if the under-seat storage 8604 is small, the secondary battery 8602 can be stored in the under-seat storage 8604. The secondary battery 8602 is removable, and when charging, the secondary battery 8602 can be carried indoors, charged, and stored before riding.

[0486] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the capacity of the secondary battery can be increased. Therefore, the secondary battery itself can be made small and lightweight. If the secondary battery itself can be made small and lightweight, it contributes to reducing the weight of the vehicle, and the cruising distance can be improved. In addition, the secondary battery mounted on the vehicle can be used as a power supply source other than the vehicle. In this case, for example, it is possible to avoid using a commercial power source during peak power demand. If it is possible to avoid using a commercial power source during peak power demand, it is possible to contribute to energy conservation and reduction of carbon dioxide emissions. In addition, if the cycle characteristics are good, the secondary battery can be used for a long period of time, and the amount of rare metals used, including cobalt, can be reduced.

[0487] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES

[0488] In this example, a positive electrode active material was produced by the production method shown in FIG. 4, and its characteristics were analyzed and evaluated.

[0489] <Preparation of positive electrode active material> The sample produced in this example will be described with reference to the production method shown in FIG.

[0490] As LiMO2 in step S14, commercially available lithium cobalt oxide (Cellseed C-10N, manufactured by Nippon Chemical Industry Co., Ltd.) having cobalt as the transition metal M and no particular additive was prepared. To this, lithium fluoride, magnesium fluoride, nickel hydroxide, and aluminum hydroxide were added and mixed by a solid phase method, similar to steps S21 to S23, S31, S32, and S41. When the number of atoms of cobalt was 100, the molecular weight of lithium fluoride was 0.33, the molecular weight of magnesium fluoride was 1, the atomic weight of nickel was 0.5, and the atomic weight of aluminum was 0.5. This was called mixture 903.

[0491] Next, annealing was performed in the same manner as in step S53. About 20 g to 60 g of the mixture 903 was placed in a square alumina container, covered, and heated in a muffle furnace to obtain a composite oxide. The annealing temperature was 900° C., 920° C., 930° C., or 950° C. The annealing time was 10 hours or 30 hours.

[0492] Next, in step S54, the composite oxide was pounded with a pestle to break the adhesion between the composite oxide particles. Then, for some samples, finely divided lithium fluoride was added and mixed. The mixture was mixed so that the molecular weight of lithium fluoride was 0.33 when the number of atoms of cobalt was 100.

[0493] Next, annealing was performed in the same manner as in step S55, with the annealing temperature being the same as in step S53.

[0494] Then, steps S54 and S55 were repeated n times, where n was 0, 1, 2, 3, or 4.

[0495] In this manner, positive electrode active materials were prepared as Samples 1 to 21. The preparation conditions are shown in Table 1. The number of annealing cycles in Table 1 indicates the total number of annealing cycles (n+1).

[0496] [Table 1]

[0497] <Surface SEM image> FIG. 36A shows a surface SEM image of Sample 2, FIG. 36B shows a surface SEM image of Sample 4, and FIG. 36C shows a surface SEM image of Sample 6.

[0498] As shown in Figure 36A, Sample 2, which was annealed once at 900°C for 10 hours, had a lot of unevenness on its surface. However, Sample 4, which was annealed twice, had fewer unevenness. Sample 6, which was annealed three times, had a smoother surface with fewer unevenness.

[0499] <Preparation of secondary battery> Secondary batteries were produced using the positive electrode active materials of Samples 1 to 21. First, the positive electrode active materials of Samples 1 to 21, AB, and PVDF were mixed in a weight ratio of active material:AB:PVDF=95:3:2 to produce a slurry, which was then applied to an aluminum current collector. NMP was used as the solvent for the slurry.

[0500] After the slurry was applied to the current collector, the solvent was evaporated. Then, pressure was applied at 210 kN / m, and then pressure was applied at 1467 kN / m. A positive electrode was obtained by the above process. The amount of the positive electrode loaded was about 7 mg / cm. 2 The density was 3.8 g / cc or more.

[0501] Using the prepared positive electrode, a coin-type battery cell of the CR2032 type (diameter 20 mm, height 3.2 mm) was produced.

[0502] Lithium metal was used as the counter electrode.

[0503] The electrolyte used in the electrolytic solution was 1 mol / L lithium hexafluorophosphate (LiPF6), and the electrolytic solution was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of EC:DEC = 3:7, to which 2 wt% vinylene carbonate (VC) was added.

[0504] The separator was made of polypropylene having a thickness of 25 μm.

[0505] The positive electrode can and the negative electrode can were made of stainless steel (SUS).

[0506] <Cycle characteristics> The charge-discharge cycle characteristics of the secondary batteries of Sample 1, Sample 3, Sample 5, Sample 7, and Sample 9, in which the annealing temperature was set to 900°C and lithium fluoride was added simultaneously with the adhesion suppression operation, are shown in Figures 37A and 37B. Figure 37A shows the discharge capacity, and Figure 37B shows the discharge capacity retention rate. The charge-discharge cycle characteristics of the secondary batteries of Sample 2, Sample 4, Sample 6, Sample 8, and Sample 10, in which lithium fluoride was not added, are shown in Figures 38A and 38B. Figure 38A shows the discharge capacity, and Figure 38B shows the discharge capacity retention rate. All were measured at 45°C. The charge was CC / CV (1C, 4.6V, 0.1C cut), and the discharge was CC (1C, 2.5V cut), with a 10-minute rest time before the next charge. In this embodiment, 1C was set to 200mA / g.

[0507] As shown in Figures 37A to 38B, one annealing cycle was insufficient as in Sample 1 and Sample 2, and good charge-discharge cycle characteristics were not obtained. Samples 3 and 4, which were annealed twice, showed slightly improved charge-discharge cycle characteristics. Samples 5 to 10, which were annealed three to five times, all showed good charge-discharge cycle characteristics. Samples 5 and 6, which were annealed three times, were particularly good. Note that the lines for Sample 6 and Sample 8 overlap in Figures 38A and 38B.

[0508] Although there was no significant difference in characteristics between the presence and absence of lithium fluoride, there was a tendency for the characteristics to be slightly better when not added.

[0509] The charge-discharge cycle characteristics of the secondary batteries of sample 6, which was subjected to annealing at 900°C for 10 hours and adhesion suppression three times, and sample 11, which was subjected to annealing at 900°C for 30 hours once, are shown in Figures 39A and 39B. Figure 39A shows the discharge capacity, and Figure 39B shows the discharge capacity retention rate. Measurements were performed at 45°C. The charge-discharge conditions were the same as those of Figures 37 and 38, except that the charge-discharge rate was 0.5C.

[0510] 39A and 39B, even though the cumulative annealing time was the same for Sample 6 and Sample 11, Sample 6 showed much better charge-discharge cycle characteristics. This is presumably because the additives in the surface layer of the positive electrode active material were better distributed by repeating the annealing and adhesion suppression operations multiple times.

[0511] The charge-discharge cycle characteristics of the secondary batteries of Sample 12, Sample 13, Sample 14, and Sample 15, in which the annealing temperature was set to 920° C., are shown in FIG. 40A and FIG. 40B. FIG. 40A shows the discharge capacity, and FIG. 40B shows the discharge capacity retention rate. The measurements were performed at 45° C. The charge-discharge conditions were the same as those shown in FIG. 37A to FIG. 38B, except that the charge-discharge rate was 0.5C.

[0512] As shown in Figures 40A and 40B, the same tendency as in Figures 37A to 38B was observed, and one annealing cycle, as in Sample 12, was insufficient, and good charge-discharge cycle characteristics were not obtained. Sample 13, which was annealed twice, showed slightly improved charge-discharge cycle characteristics. Samples 14 and 15, which were annealed three and four times, both showed good charge-discharge cycle characteristics. In particular, Sample 14, which was annealed three times, was the best.

[0513] The charge-discharge cycle characteristics of the secondary batteries of Sample 16, Sample 17, and Sample 18, in which the annealing temperature was set to 930° C., are shown in FIG. 41A and FIG. 41B. FIG. 41A shows the discharge capacity, and FIG. 41B shows the discharge capacity retention rate. The measurements were performed at 45° C. The charge-discharge conditions were the same as those shown in FIG. 37A to FIG. 38B, except that the charge-discharge rate was set to 0.5C.

[0514] As shown in Figures 41A and 41B, the same trends as those in Figures 37A to 38B and Figures 40A and 40B were observed. A single annealing cycle, as in Sample 16, was insufficient and good charge-discharge cycle characteristics were not obtained. Samples 17 and 18, which were annealed two and three times, both showed good charge-discharge cycle characteristics. In particular, Sample 18, which was annealed three times, was the best.

[0515] The charge-discharge cycle characteristics of the secondary batteries of Sample 19, Sample 20, and Sample 21, in which the annealing temperature was set to 950° C., are shown in FIG. 42A and FIG. 42B. FIG. 42A shows the discharge capacity, and FIG. 42B shows the discharge capacity retention rate. Measurements were performed at 45° C. The charge-discharge conditions were the same as those shown in FIG. 37A to FIG. 38B, except that the charge-discharge rate was 0.5C.

[0516] As shown in Figures 42A and 42B, the same trends as Figures 37A to 38B and Figures 40A to 41B were observed. A single annealing cycle was insufficient as in Sample 19, and good charge-discharge cycle characteristics were not obtained. Samples 20 and 21, which were annealed two and three times, both showed good charge-discharge cycle characteristics.

[0517] Table 2 shows the initial discharge capacities and the discharge capacity retention rates after 30 or 50 cycles for Samples 1 to 21.

[0518] [Table 2]

[0519] As shown in Table 2, when the annealing temperature was 900°C or higher and 930°C or lower, the cycle characteristics tended to improve.

[0520] As described above, it was shown that a positive electrode active material that exhibits favorable cycle characteristics even at a relatively high temperature of 45° C. can be manufactured by the method for manufacturing a positive electrode active material according to one embodiment of the present invention. [Explanation of symbols]

[0521] 100: positive electrode active material, 100a: surface layer, 100b: inside, 110: rotary kiln, 110a: rotary kiln, 110b: rotary kiln, 110c: kiln, 111: kiln body, 111a: kiln body, 111b: kiln body, 112: heating means, 112a: heating means, 112b: heating means, 113: raw material supply means, 113a: raw material supply means, 113b: raw material supply means, 114: discharge section, 115: control panel, 116: atmosphere control means, 117: blade, 120: measuring device, 120a: measuring device, 120b: measuring device, 130: mill, 131a: mill, 131b: mill, 150: roller hearth kiln, 150a: roller hearth kiln , 151: kiln body, 152: roller, 153a: heating means, 153b: heating means, 154: atmosphere control means, 155: adhesion suppression means, 155a: adhesion suppression means, 155b: adhesion suppression means, 155c: adhesion suppression means, 157a: shield plate, 157b: shield plate, 157c: shield plate, 158: raw material supply means, 160: container, 160a: container, 161: workpiece, 170: mesh belt kiln, 171: kiln body, 172: adhesion suppression means, 173: heating means, 174: mesh belt, 180: muffle furnace, 181: hot plate, 182: heating means, 183: heat insulating material, 184: atmosphere control means, 185: adhesion suppression means, 190: container, 191: workpiece

Claims

[Claim 1] A roller hearth kiln for continuously treating a workpiece contained in a container, The roller hearth kiln has a tunnel-shaped kiln body, a plurality of rollers, a first heating means, a second heating means, and an adhesion suppression means, The plurality of rollers have a function of transporting the container, The kiln body has an upstream portion and a downstream portion along the conveying direction of the plurality of rollers, The first heating means has a function of heating the upstream portion to 800° C. or more and 1100° C. or less, The second heating means has a function of heating the downstream portion to 500° C. or more and 1130° C. or less, The adhesion suppression means has a function of vibrating the container.

Citation Information

Patent Citations

  • Production of spherical lithium-nickel complex oxide and nonaqueous electrolyte cell using the same as positive electrode

    JP1998087332A

  • Lithium-manganese oxide for positive electrode of lithium secondary battery and its manufacture

    JP1999307098A

  • Rotary kiln apparatus and pyrolizing facility

    JP2005273926A

  • Method of continuously manufacturing electrode material

    JP2012048968A

  • Heat treatment device of dihydrate gypsum, and method for producing mixed gypsum

    JP2013167423A